Composite particles containing hydrophobic dyes and amphiphilic block copolymers and their use in optical applications - Patents.com
Patent Information
- Application Number
- JP2022516248
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2019-05-24
- Filing Date
- 2020-05-25
- Publication Date
- 2025-02-21
- Estimated Expiration
- 2040-05-25
AI Technical Summary
【0021】 本開示の他の特徴及び利点は、以下の詳細な説明から明らかになるであろう。しかし、詳細な説明及び特定の例は、出願の実施形態を示すが、例示としてのみ与えられ、特許請求の範囲は、これらの実施形態によって限定されるべきではなく、全体としての説明と一致する、最も広い解釈を与えられるべきであることを理解すべきである。
Smart Images

Figure 0007634522000027 
Figure 0007634522000028 
Figure 0007634522000029
Abstract
Description
[Technical field]
[0001] The present disclosure relates to composite particles comprising one or more hydrophobic dyes and one or more amphiphilic block copolymers, as well as compositions comprising such composite particles and their use, for example, optionally for selectively filtering light in contact lenses, including hydrogel-based and silicone hydrogel-based contact lenses. The present disclosure also relates to ophthalmic lenses comprising one or more composite particles or one or more compositions of the present disclosure. [Background technology]
[0002] An optical filter is a device with wavelength selective transmission that acts on a light source or receiver of light. Such filters can be configured to transform aspects of color appearance as seen by the human eye or any recording device. Optical filters are useful in fields including, but not limited to, vision care, medical procedures, ophthalmic lens development, cinematography, and entertainment, among others, in situations where certain wavelengths of light need to be controlled, modulated, or attenuated. For example, optical filters in ophthalmic lenses can provide eye protection from high energy radiation in the ultraviolet (UV), visible, and / or infrared spectrum. Optical filters can also provide cosmetic benefits, such as color balancing to improve color enhancement for aesthetics or entertainment in contact lenses, or to achieve a desired visual effect. Additionally, optical filters can be useful in medical applications of ophthalmic lenses, such as modifying the human spectral response associated with short (S), intermediate (M), and long (L) cone cell photoreceptors for use in treating genetic and / or non-genetic vision conditions, such as color blindness or myopia.
[0003] Currently, there are two different methods for preparing optical filtering contact lenses containing light filtering additives such as pigments. The first method is to incorporate the pigment into the contact lens by immersing a hydrated or non-hydrated lens in a bath of pigment and solvent. This method can lead to migration of the pigment molecules from the bulk, hydrogel material, loss or reduction of optical filtering ability, and potential health concerns due to release of the pigment into the eye.
[0004] The second method is to incorporate the dye into the contact lens by directly curing a solution of contact lens monomer containing the dye, where the dye has been specifically functionalized to react with the contact lens monomer. For example, the dye can be functionalized with vinylsulfonyl or halogen triazine groups. Attempts to polymerize the dye with the hydrogel monomer can greatly reduce migration of the dye molecules from the bulk hydrogel material, but there are only a limited number of commercially valuable dyes that have the correct local chemistry required for covalent attachment to the bulk hydrogel material. When applying this method to non-functionalized dyes, elaborate de novo redesign and modification of the dye is often required to satisfy the covalent attachment within the bulk hydrogel material. Furthermore, synthetically altering non-functionalized dyes in this way can change the natural absorption spectrum of the dye, making it less suitable for use as an optical filter for the selected desired application.
[0005] For example, the light absorbing pigment zinc(II) tetraphenylporphyrin (Zn(II)TPP) has optical properties that make it commercially valuable as an HEV / blue light blocking agent in contact lenses. However, Zn(II)TPP does not have the correct local chemistry required for direct covalent attachment to bulk hydrogel materials. Synthetically modifying Zn(II)TPP to provide the correct functionalization eliminates, reduces, and / or alters its HEV / blue light blocking capabilities.
[0006] Depending on the particular setting in which the light absorbing additive is used, various challenges arise from this method which require different characteristics of the dyes used.
[0007] For example, pigments that are incorporated into contact lens monomers may be subjected to many harsh lens manufacturing processes and conditions, such as photocuring with UV / HEV light, thermal curing through the application of heat, and / or catalyst initiated polymerization through the incorporation of a polymerization catalyst into the bulk contact lens monomer. Additionally, during use, contact lenses containing pigments may be exposed to harmful UV / HEV radiation from natural and / or man-made sources.
[0008] The manufacture of hydrogel-based contact lenses often involves photocuring through the use of UV / HEV light, which can degrade the optical properties of the dyes, rendering many dyes less useful for optical filtering applications in contact lenses.
[0009] Additionally, during lens manufacturing, the pigments may be subjected to various organic solvent extractions, solvent washes, hydration, autoclave sterilization, and / or extended exposure to high or low temperatures during manufacturing. One of the solvents used during the manufacture of contact lenses is ethanol. Summary of the Invention [Problem to be solved by the invention]
[0010] The present disclosure relates to composite particles, compositions comprising such composite particles, and methods for their preparation. The present disclosure also relates to their use as optical filters in contact lenses, and methods of optical filtering in contact lenses. The present disclosure further relates to contact lenses comprising the composite particles or compositions thereof. [Means for solving the problem]
[0011] Thus, in one aspect, the present disclosure provides a method for producing a method for treating a cancer cell comprising: A hydrophobic dye; Hydrophobic dye-encapsulated amphiphilic block copolymers and wherein the hydrophobic dye has an absorbance ranging from the ultraviolet to the infrared region of the electromagnetic spectrum.
[0012] In another aspect, the present disclosure includes a composition comprising composite particles of the present disclosure in a solvent selected from an aqueous solvent, an organic solvent, and combinations thereof.
[0013] In another aspect, the present disclosure includes contact lenses comprising one or more composite particles or compositions of the present disclosure.
[0014] In another aspect, the present disclosure includes a composite particle or composition of the present disclosure for use as an optical filter, optionally in a contact lens, which is optionally hydrogel or silicone hydrogel based.
[0015] In another aspect, the present disclosure includes the use of one or more composite particles or compositions of the present disclosure as an optical filter, optionally in a contact lens.
[0016] In another aspect, the present disclosure includes a method of optical filtering comprising the step of selectively blocking optical radiation using one or more composite particles or compositions of the present disclosure.
[0017] In another aspect, the present disclosure provides a method of preparing a composition of the present disclosure, comprising: preparing a dye / polymer solution comprising a hydrophobic dye and an amphiphilic block copolymer in an organic solvent; adding the dye / polymer solution to water with mixing to obtain the composition as an aqueous micellar solution; The present invention includes a method comprising the steps of:
[0018] In another aspect, the present disclosure provides a method for preparing a composition of the present disclosure comprising composite particles of the present disclosure in an aqueous solution, the method comprising: preparing a dye / polymer / crosslinker solution comprising a hydrophobic dye, an amphiphilic block copolymer, and one or more crosslinkers in an organic solvent; adding the dye / polymer / crosslinker solution to water while mixing to obtain an aqueous micellar solution; The present invention includes a method comprising the steps of:
[0019] The method of preparing the composite particles of the present disclosure comprises: preparing a dye / polymer solution comprising a hydrophobic dye and an amphiphilic block copolymer in an organic solvent; adding the dye / polymer solution to water with mixing to obtain composite particles in aqueous solution; Optionally, obtaining the composite particles from the aqueous solution by filtration. Includes.
[0020] The method of preparing the composite particles of the present disclosure comprises: preparing a dye / polymer / crosslinker solution comprising a hydrophobic dye, an amphiphilic block copolymer, and a crosslinker in an organic solvent; adding the dye / polymer / crosslinker solution to water with mixing to obtain an aqueous solution; Optionally, obtaining the composite particles from the aqueous solution by filtration. Includes.
[0021] Other features and advantages of the present disclosure will become apparent from the following detailed description. However, it should be understood that the detailed description and specific examples, while indicating embodiments of the application, are given by way of illustration only, and that the claims should not be limited by these embodiments, but should be given the broadest interpretation consistent with the description as a whole.
[0022] Embodiments of the present application will now be described in more detail with reference to the accompanying drawings in which: [Brief description of the drawings]
[0023] [Figure 1] 1 illustrates an exemplary representation of an encapsulation process according to one embodiment of the present disclosure. [Diagram 2] 1 shows a comparison between the ultraviolet-visible (UV-Vis) absorption spectra of the dye Epoliget™ 5843 with and without encapsulation. [Figure 3A]Figure 1 shows the physical appearance of the dye Epoliget™ 5843 without and with encapsulation. Panel A shows the insoluble dye in water without encapsulation. [Figure 3B] Figure 1 shows the physical appearance of the dye Epoliget™ 5843 with and without encapsulation. Panel B shows the dye dissolved in tetrahydrofuran (THF). [Figure 3C] Figure 1 shows the physical appearance of the dye Epoliget™ 5843 without and with encapsulation. Panel C shows an exemplary image of the encapsulated dye in an aqueous medium. [Figure 4A] 1 shows the spectral data and physical appearance of a composite particle composition including the dye Exciton ABS594 according to an embodiment of the present disclosure. Panel A shows a comparison between the UV-Vis absorption spectra of the dye without and with encapsulation. [Figure 4B] 1 shows the spectral data and physical appearance of a composite particle composition including the dye Exciton ABS594 according to an embodiment of the present disclosure. Panel A shows a calibration curve of the encapsulated dye in 10% THF and 90% water. [Figure 5A] 1 shows the spectral data and physical appearance of a composite particle composition including the dye Exciton ABS456 according to an embodiment of the present disclosure, Panel A shows a comparison between the UV-Vis absorption spectra of the dye without and with encapsulation. [Figure 5B] 1 shows the spectral data and physical appearance of a composite particle composition including the dye Exciton ABS456 according to an embodiment of the present disclosure. Panel A shows a calibration curve of the encapsulated dye in 10% THF and 90% water. [Figure 6A] 1 shows exemplary transmission electron microscopy (TEM) images and dynamic light scattering (DLS) results of composite particles including the dye Exciton ABS594 according to embodiments of the present disclosure. Panel A shows a TEM image of a composite particle including the dye Exciton ABS594. The scale bar indicates 100 nm. [Figure 6B]Panel A shows exemplary transmission electron microscopy (TEM) images and dynamic light scattering (DLS) results of composite particles including the dye Exciton ABS594 according to embodiments of the present disclosure. Panel B shows DLS results of composite particles including the dye Exciton ABS594. [Figure 7A] 1 shows exemplary transmission electron microscopy (TEM) images and dynamic light scattering (DLS) results of composite particles including the dye Exciton ABS456 according to embodiments of the present disclosure. Panel A shows a TEM image of a composite particle including the dye Exciton ABS456. The scale bar indicates 200 nm. [Figure 7B] Panel A shows exemplary transmission electron microscopy (TEM) images and dynamic light scattering (DLS) results for composite particles including the dye Exciton ABS456 according to embodiments of the present disclosure. Panel B shows DLS results for composite particles including the dye Exciton ABS456. [Figure 8] 1 shows the UV-Vis absorbance spectrum of a composition of Exciton ABS594 composite particles and Exciton ABS456 composite particles according to one embodiment of the present disclosure. [Figure 9A] 1 shows UV-Vis absorbance spectra of composite particle compositions formed using basic encapsulation procedures 1, 2, and 3, according to embodiments of the present disclosure. Panel A shows a comparison of free dye and a composite particle composition formed using a syringe pump (basic encapsulation procedure 2). [Figure 9B] FIG. 1 shows UV-Vis absorbance spectra of composite particle compositions formed using basic encapsulation procedures 1, 2, and 3, according to embodiments of the present disclosure. Panel B shows a comparison of composite particle compositions formed using a syringe pump (basic encapsulation procedure 2) and a Pasteur pipette (basic encapsulation procedure 1). [Figure 9C] Figure 1 shows UV-Vis absorbance spectra of composite particle compositions formed using basic encapsulation procedures 1, 2, and 3, according to embodiments of the present disclosure. Panel C shows a comparison of composite particle compositions formed using a syringe pump (basic encapsulation procedure 2) and FNP (basic encapsulation procedure 3). [Figure 10]1 shows an overlay of UV-Vis spectra of an Exciton ABS456 composite particle composition at different time points (1 day, 1 week, 3 weeks, 7 weeks, and 11 weeks) according to an embodiment of the present disclosure. [Figure 11A] FIG. 1 shows the results of a UV stability test of an Exciton ABS456 composite particle composition and free dye according to an embodiment of the present disclosure. Panel A shows a comparison between the UV-Vis absorbance spectra of the free dye before and after UV exposure for various times (10, 20, or 30 minutes). [Figure 11B] 1 shows the results of a UV stability test of an Exciton ABS456 composite particle composition and free dye according to an embodiment of the present disclosure. Panel A shows a comparison between the UV-Vis absorbance spectra of the composite particle composition before and after UV exposure. [Figure 12A] 1 shows DLS results of an Exciton ABS456 composite particle composition before and after UV exposure, according to one embodiment of the present disclosure. Panel A shows the number distribution of the composite particle composition before UV exposure. [Figure 12B] 1 shows DLS results of an Exciton ABS456 composite particle composition before and after UV exposure, according to one embodiment of the present disclosure. Panel A shows the intensity distribution of the composite particle composition before UV irradiation. [Figure 12C] 1 shows DLS results of an Exciton ABS456 composite particle composition before and after UV exposure, according to one embodiment of the present disclosure. Panel C shows the number distribution of the composite particle composition after UV irradiation. [Figure 12D] 1 shows DLS results of an Exciton ABS456 composite particle composition before and after UV exposure, according to one embodiment of the present disclosure. Panel D shows the intensity distribution of the composite particle composition after UV irradiation. [Figure 12E] FIG. 1 shows DLS results of an Exciton ABS456 composite particle composition before and after UV exposure, according to one embodiment of the present disclosure. Panel E shows scanning electron microscope (SEM) images of the composite particles before and after UV irradiation. The SEM scale bar indicates 5 μm. [Figure 12F]FIG. 1 shows DLS results of an Exciton ABS456 composite particle composition before and after UV exposure, according to one embodiment of the present disclosure. Panel F shows scanning electron microscope (SEM) images of the composite particles before and after UV irradiation. The SEM scale bar indicates 5 μm. [Figure 13] 1 shows a comparison of the UV-Vis spectra of an Exciton ABS456 composite particle composition according to one embodiment of the present disclosure before and after heating. [Figure 14] 1 shows the absorbance spectra of an Exciton ABS594 composite particle composition according to one embodiment of the present disclosure before and after heating. [Figure 15A] Figure 1 shows UV-Vis spectra of Exciton ABS456 composite particle compositions according to embodiments of the present disclosure in different concentrations of THF / water at different times and after UV fading. Panel A shows the UV-Vis spectra of the composite particle composition in 35% v / v THF after various times of UV irradiation. [Figure 15B] Panel A shows the UV-Vis spectra of the Exciton ABS456 composite particle composition according to an embodiment of the present disclosure in different concentrations of THF / water at different time points and after UV fading. Panel B shows the UV-Vis spectra of the composite particle composition in 10% v / v THF after various times of UV irradiation. [Figure 15C] Panel A shows the UV-Vis spectra of the Exciton ABS456 composite particle composition according to the present disclosure in different concentrations of THF / water at different time points and after UV fading. Panel B shows the UV-Vis spectra of the composite particle composition in 64% v / v THF after various times of UV irradiation. [Figure 15D] Panel A shows the UV-Vis spectra of an Exciton ABS456 composite particle composition according to an embodiment of the present disclosure in different concentrations of THF / water at different time points and after UV fading. Panel B shows the UV-Vis spectra of a composite particle composition in 99% v / v THF after various times of UV irradiation. [Figure 16] 1 shows optical images of polyacrylamide gels doped with ABS594 and ABS456 encapsulated dye micelles, according to an embodiment of the present disclosure. [Figure 17] 1 shows the absorbance spectra of polyacrylamide gels doped with ABS594 and ABS456 encapsulated dye micelles, according to an embodiment of the present disclosure. [Figure 18] Shown are UV-Vis absorbance spectra of composite particles prepared using direct injection (A), flash nanoprecipitation (B), ultrasonic method (C) and vortex method (D). [Figure 19] 1 shows the UV-Vis absorbance of the amphiphilic block copolymer, free dye, and dye + amphiphilic block copolymer after flocculation with calcium chloride. [Figure 20A] TEM images of composite particles containing different dyes. 1,3,5,7-tetramethyl-8-(4-hydroxyphenyl)BODIPY (A) is shown; [Figure 20B] TEM images of composite particles containing different dyes. 1,7-(di-4,N,N-dimethylaminophenyl)-3,5-(di-4-bromophenyl) AZABODIPY (B) is shown; [Figure 20C] TEM images of composite particles containing different dyes. Shown is 2,3,7,8,12,13,17,18-(octabromo)-5,10,15,20-(tetraphenyl)porphyrin (C); [Figure 20D] TEM images of composite particles containing different dyes. Zinc(II) 2,9,16,23-(tetranitro)phthalocyanine (D) is shown; [Figure 20E] TEM images of composite particles containing different dyes are shown. Coumarin 153 (E) is shown; [Figure 20F] TEM images of composite particles containing different pigments. Vitamin E (F) is shown; [Figure 20G] TEM images of composite particles containing different pigments. β-carotene (G) is shown; [Figure 20H] TEM images of composite particles containing different dyes. Perylene (H) is shown; [Figure 20I] TEM images of composite particles containing different dyes. P-Quaterphenyl(I) is shown; [Figure 20J] TEM images of composite particles containing different dyes. Vanadyl 2,3-naphthalocyanine (J) is shown; [Figure 20K] Figure 1 shows TEM images of composite particles containing different dyes: 2-[3-(2H-benzotriazol-2yl)-4-hydroxy-phenyl]ethyl methacrylate (NORBLOC brand) (K). [Figure 21A] Figure 1 shows the UV-Vis absorbance of composite particles containing different dyes. 1,3,5,7-tetramethyl-8-(4-hydroxyphenyl) BODIPY (A) is shown; [Figure 21B] Figure 2 shows the UV-Vis absorbance of composite particles containing different dyes. 1,7-(di-4,N,N-dimethylaminophenyl)-3,5-(di-4-bromophenyl) AZABODIPY (B) is shown; [Figure 21C] Figure 1 shows the UV-Vis absorbance of composite particles containing different dyes. Shown is 2,3,7,8,12,13,17,18-(octabromo)-5,10,15,20-(tetraphenyl)porphyrin (C); [Figure 21D] Figure 1 shows the UV-Vis absorbance of composite particles containing different dyes. Zinc(II) 2,9,16,23-(tetranitro)phthalocyanine (D) is shown; [Figure 21E] Figure 1 shows the UV-Vis absorbance of composite particles containing different dyes. Coumarin 153 (E) is shown; [Figure 21F] Figure 1 shows the UV-Vis absorbance of composite particles containing different pigments. Vitamin E (F) is shown; [Figure 21G] Figure 2 shows the UV-Vis absorbance of composite particles containing different pigments. β-carotene (G) is shown; [Fig. 21H] Figure 1 shows the UV-Vis absorbance of composite particles containing different dyes. Perylene (H) is shown; [Figure 21I] UV-Vis absorbance of composite particles containing different dyes. P-Quaterphenyl(I) is shown; [Figure 21J] UV-Vis absorbance of composite particles containing different dyes. Vanadyl 2,3-naphthalocyanine (J) is shown; [Figure 21K] Figure 1 shows the UV-Vis absorbance of composite particles containing different dyes, 2-[3-(2H-benzotriazol-2yl)-4-hydroxy-phenyl]ethyl methacrylate (NORBLOC brand) (K). [Figure 22A] Panel A shows the 29Si solid-state NMR spectrum of TEOS cross-linked composite particles containing zinc(II) 5,10,15,20-(tetraphenyl)porphyrin. Panel B shows the spectrum of poly(styrene) 1300-b-poly(ethylene oxide) 5600 cross-linked with TEOS. [Figure 22B] Panel A shows the 29Si solid-state NMR spectrum of TEOS-crosslinked composite particles containing zinc(II) 5,10,15,20-(tetraphenyl)porphyrin. Panel B shows the spectrum of poly(1,2-butadiene) 15000-b-poly(acrylic acid) 6500 crosslinked with TEOS. [Figure 22C] Panel A shows the 29Si solid-state NMR spectrum of TEOS-crosslinked composite particles containing zinc(II) 5,10,15,20-(tetraphenyl)porphyrin. Panel B shows the spectrum of poly(1,2-butadiene) 31500-b-poly(methyl methacrylate) 21000 crosslinked with TEOS. [Figure 22D] Panel A shows the 29Si solid-state NMR spectrum of TEOS-crosslinked composite particles containing zinc(II) 5,10,15,20-(tetraphenyl)porphyrin. Panel B shows the spectrum of a control sample. [Diagram 23]SEM and TEM images of TEOS crosslinked composite particles are shown: 15000 poly(1,2-butadiene) crosslinked with 1x, 2x, or 5x the mass of TEOS relative to the mass of the hydrophilic polymer block (left to right in Panel A); 31500 poly(1,2-butadiene) crosslinked with 1x, 2x, or 5x the mass of TEOS relative to the mass of the hydrophilic polymer block (b-poly(acrylic acid)) (left to right in Panel A); 21500 poly(1,2-butadiene) crosslinked with 1x, 2x, or 5x the mass of TEOS relative to the mass of the hydrophilic polymer block (b-poly(methyl methacrylate)). 000 (left to right in Panel B); poly(styrene) 1300-b-poly(ethylene oxide) 5600 crosslinked with 1x, 2x, or 5x the mass of TEOS relative to the mass of the hydrophilic polymer block (left to right in Panel C); poly(vinyl alcohol) 2300-b-poly(methyl methacrylate) 25000 crosslinked with 1x, 2x, or 5x the mass of TEOS relative to the mass of the hydrophilic polymer block (left to right in Panel D). [Figure 24] Figure 1 shows the UV-Vis absorbance of composite particles poly(1,2-butadiene) 31500-b-PMMA 21000 containing zinc(II) 5,10,15,20-(tetraphenyl)porphyrin lyophilized with the cryoprotectant PEG4000. [Diagram 25] 1 shows the UV-Vis absorbance spectra of various composite particles in M2Dx prepolymer solution. [Figure 26] 1 shows a representative photograph of polymerized M2Dx gel containing composite particles of the present disclosure. [Figure 27] 1 shows the UV-Vis absorbance of M2Dx polymer gels containing different composite particles (CS28-42), comparative particles (BC01, PH01, PN01) and control particles (CS00). [Figure 28] The left side of each panel shows the UV-Vis absorbance of M2Dx polymer gels containing CS34 (A), CS37 (B), CS41 (C) or CS42 (D) composite particles after 95% ethanol extraction, and the right side of each panel shows the UV-Vis absorbance spectrum of the corresponding 95% ethanol wash. [Figure 29]Representative UV-Vis absorbance spectra of autoclaved M2Dx polymer gels containing different composite particles, including gels containing CS38, CS39, CS40, and CS41. [Diagram 30] 1 shows the UV-Vis absorbance after autoclaving of saline in which M2Dx polymer gels containing different composite particles were autoclaved. [Figure 31A] 1 shows UV-Vis of composite particles after exposure to different solvents. Panel A shows composite particle PN01 after exposure to ethanol. [Figure 31B] 1 shows the UV-Vis of composite particles after exposure to different solvents. Panel A shows composite particle CS19 after exposure to ethanol. [Figure 31C] 1 shows the UV-Vis of composite particles after exposure to different solvents. Panel C shows composite particle CS29 after exposure to ethanol. [Figure 31D] 1 shows the UV-Vis of composite particles after exposure to different solvents. Panel D shows composite particle CS31 after exposure to ethanol. [Figure 31E] 1 shows UV-Vis of composite particles after exposure to different solvents. Panel E shows composite particle CS33 after exposure to ethanol. [Fig. 31F] 1 shows the UV-Vis of composite particles after exposure to different solvents. Panel F shows composite particle CS34 after exposure to ethanol. [Figure 31G] Panel G shows the UV-Vis absorbance spectra of composite particle CS20 after exposure to different solvents. [Fig. 31H] Panel H shows the UV-Vis absorbance spectra of composite particle CS22 after exposure to different solvents. [Fig. 31I] 1 shows the UV-Vis of composite particles after exposure to different solvents. Panel I shows the UV-Vis absorbance spectra of composite particle CS04 after exposure to different solvents. [Diagram 32]Representative UV-Vis absorbance of M2Dx polymer gel containing composite particles CS35 after 1, 2, 3, 4 or 5 minutes of photobleaching is shown. [Diagram 33] 1 shows UV-Vis absorbance spectra of saline after photoaging of M2Dx polymer gels containing different composite particles in saline. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0024] Description of Various Embodiments I. Definition Unless otherwise indicated, the definitions and embodiments described in this and other sections are intended to be applicable to all embodiments and aspects of the disclosure described herein that are suitable as understood by one of ordinary skill in the art.
[0025] As used in this disclosure, the singular forms "a," "an," and "the" include plural referents unless the content clearly dictates otherwise.
[0026] As used herein, the terms "about," "substantially," and "approximately" refer to a reasonable amount of deviation from the modified term so that the end result is not significantly altered. These degrees of deviation should be interpreted to include deviations of at least ±5% of the modified term, unless this deviation negates the meaning of the word it modifies or the context suggests otherwise to one of ordinary skill in the art.
[0027] This specification refers to a number of chemical terms and abbreviations used by those of ordinary skill in the art. Nonetheless, definitions of selected terms are provided for clarity and consistency.
[0028] The term "hydrophobic" as used herein, for example in "hydrophobic dyes," refers to the property of a molecule or portion thereof to not be attracted to water molecules. For example, the property includes repelling water, tending not to bond with water, or not being able to completely dissolve in water. For example, when referring to a hydrophobic dye, the term hydrophobic can mean that the dye is substantially insoluble in water, but may be soluble in water-miscible organic solvents.
[0029] As used herein, the term "hydrophilic" refers to the property of a molecule or portion thereof to be attracted to water molecules.
[0030] As used herein, the term "optionally substituted" refers to a group, structure, or molecule that is unsubstituted or substituted with one or more substituents.
[0031] The term "amphiphilic copolymer" as used herein refers to a copolymer that includes subunits or monomers with different hydrophobic and hydrophilic properties. For example, when subunits or monomers of the same properties are present in blocks of the same copolymer chain, the copolymer is called a block copolymer. For example, an amphiphilic block copolymer includes blocks in which one or more blocks include one or more types of hydrophilic subunits or monomers and other blocks include one or more types of hydrophobic subunits or monomers, each block being substantially hydrophilic or hydrophobic. It is possible for one or more types of hydrophilic or hydrophobic subunits or monomers to be dispersed throughout the copolymer, yet produce a block that is substantially hydrophilic or hydrophobic overall.
[0032] The term "hydrogel" as used herein refers to a gel in which the swelling agent is water. In some embodiments, hydrogel refers to a gel that includes a polymer network material with an equilibrium water content of at least 10% w / w. Hydrogels that include a silicone component are referred to herein as "silicone hydrogels."
[0033] As used herein, the term "blue light" refers to the high energy blue portion of the spectrum. For example, it can refer to the portion of the spectrum in the range of approximately 380 nm to 500 nm.
[0034] As used herein, terms such as "selectively block light" or "selectively blocking light" refer to providing a minimum transmission in a selected portion of the spectrum.
[0035] II. Composite particles, compositions and uses thereof In one aspect, the present disclosure provides a method for producing a method for manufacturing a semiconductor device comprising: A hydrophobic dye; Hydrophobic dye-encapsulated amphiphilic block copolymers and wherein the hydrophobic dye has an absorbance ranging from the ultraviolet to the infrared region of the electromagnetic spectrum.
[0036] In some embodiments, the amphiphilic block copolymer is crosslinked, e.g., by one or more crosslinking agents.
[0037] In some embodiments, the composite particles are synthetic polymeric micelles.
[0038] The hydrophobic dye is any suitable hydrophobic dye having an absorbance ranging from the ultraviolet to the infrared region of the electromagnetic spectrum. In some embodiments, the hydrophobic dye is a laser dye or an absorber dye. In one embodiment, the hydrophobic dye is a laser dye. One skilled in the art will appreciate that laser dye solutions absorb at shorter wavelengths and emit at longer wavelengths. In another embodiment of the present disclosure, the hydrophobic dye is an absorber dye.
[0039] In some embodiments, the hydrophobic dye is selected from coumarins, fluoresceins, rhodamines, pyrromethenes, cyanines, carbocyanines, flavins, oxazines, carbazines, stilbenes, diphenylstilbenes, oxazoles, diphenyls, terphenyls, quaterphenyls, polyphenyls, phenyloxazones, phenoxazoniums, pyridines, pyridiniums, carotenoids, retinoids, porphyrins, phthalocyanines, benzophenones, metal oxides, benzotriazoles, tocopherols, tocotrienols, anthracenes, perylenes, polycyclic aromatic hydrocarbons (PAHs), polyenes, corrins, chlorines, corns, indolenines, chlorophylls, azo dyes, polymethines, diarylmethanes, triarylmethanes, polyenes, anthracinediones, pyrazolones, anthraquinones, pyrans, phenothiazines, triazines, oxalanilides, acridines, benzanthrones, and combinations thereof. In some embodiments, the hydrophobic dye is selected from BODIPY, AzaBODIPY, tetraphenylporphyrin, phthalocyanine, naphthalocyanine, coumarin, benzotriazole, tocopherol, tocotrienol, carotenoid, anthracene, perylene, metal oxide, and combinations thereof. In some embodiments, the hydrophobic dye is selected from 1,3,5,7-tetramethyl-8-(4-hydroxyphenyl)BODIPY, 1,7-(di-4-N,N-dimethylaminophenyl)-3,5-(di-4-bromophenyl)AZABODIPY, 2,3,7,8,12,13,17,18-(octabromo)-5,10,15,20-(tetraphenyl)porphyrin, Zn(II)5,10,15,20-tetraphenyl-21H,23 H-porphyrin (Zn(II)TPP), Zn(II) 2,9,16,23-(tetranitro)phthalocyanine, coumarin 153, 2-(2'hydroxy-5'-methacryloxyethylphenyl)-2H-benzotriazole, vitamin E, β-carotene, 9,10-diphenylanthracene, perylene, chromium(III) oxide, P-quaterphenyl, vanadyl 2,3-naphthalocyanine, and combinations thereof.In some embodiments, the hydrophobic dye is Zn(II) 5,10,15,20-tetraphenyl-21H,23H-porphyrin (Zn(II)TPP).
[0040] The amphiphilic block copolymer is any suitable amphiphilic block copolymer that encapsulates the hydrophobic dye. In some embodiments, the amphiphilic block copolymer is a poly(alkyl acrylate)-based copolymer, a poly(alkyl methacrylate)-based copolymer, a poly(acrylic acid)-based copolymer, a poly(methacrylic acid)-based copolymer, a poly(diene)-based copolymer, a poly(N-isopropylacrylamide)-based copolymer, a poly(ethylene glycol)-based copolymer, a poly(methyleneindane)-based copolymer, a poly(siloxane)-based copolymer, a poly(styrene)-based copolymer, a substituted poly(styrene)-based copolymer, a poly(vinylpyridine)-based copolymer, a poly(vinyl alcohol)-based copolymer, a poly(alkyl acrylate)-based copolymer, a poly(alkylene oxide)-based copolymer, a poly(dialkylsiloxane)-based copolymer, a poly(olefin)-based copolymer, a poly(alkylene oxide diacrylate)-based copolymer, a poly(butanediol diacrylate)-based copolymer, or a combination thereof. In some embodiments, the amphiphilic block copolymer is a poly(alkyl acrylate)-based copolymer, a poly(alkyl methacrylate)-based copolymer, a poly(acrylic acid)-based copolymer, a poly(methacrylic acid)-based copolymer, a poly(diene)-based copolymer, a poly(olefin)-based copolymer, a poly(ethylene glycol)-based copolymer, a poly(siloxane)-based copolymer, a poly(styrene)-based copolymer, a poly(vinyl alcohol)-based copolymer, a poly(dialkylsiloxane)-based copolymer, or a combination thereof. In some embodiments, the amphiphilic block copolymer is a poly(methyl acrylate)-based copolymer, a poly(n-butyl acrylate)-based copolymer, a poly(methyl methacrylate)-based copolymer, a poly(tert-butyl methacrylate)-based copolymer, a poly(acrylic acid)-based copolymer, a poly(methacrylic acid)-based copolymer, a poly(1,2-butadiene)-based copolymer, a poly(1,4-butadiene)-based copolymer, a poly(styrene)-based copolymer, a poly(dimethylsiloxane)-based copolymer, a poly(vinyl alcohol)-based copolymer, a poly(propylene oxide)-based copolymer, or a combination thereof.
[0041] In some embodiments, the amphiphilic block copolymer is a diblock copolymer or a triblock copolymer, or a combination thereof. In some embodiments, the amphiphilic block copolymer is a diblock copolymer. In some embodiments, the amphiphilic block copolymer is poly(ethylene glycol)-b-poly(styrene), poly(n-butyl acrylate)-b-poly(acrylic acid), or poly(methyl methacrylate)-b-poly(methacrylic acid). In some embodiments, the amphiphilic block copolymer is poly(1,2-butadiene)-b-poly(acrylic acid), poly(1,2-butadiene)-b-poly(ethylene oxide), poly(1,2)-butadiene)-b-poly(methacrylic acid), poly(1,2-butadiene)-b-poly(methyl methacrylate), poly(1,2-butadiene)-b-poly(vinyl alcohol), poly(1,2-butadiene-co-1,4-butadiene)-b-poly(acrylic acid), poly(1,2-butadiene-co-1,4-butadiene)-b-poly(methacrylic acid), poly(1,2-butadiene-co-1,4-butadiene) ... Poly(1,2-butadiene-co-1,4-butadiene)-b-poly(ethylene oxide), poly(1,2-butadiene-co-1,4-butadiene)-b-poly(methacrylic acid), poly(1,2-butadiene-co-1,4-butadiene)-b-poly(vinyl alcohol), poly(1,4-butadiene)-b-poly(acrylic acid), poly(1,4-butadiene)-b-poly(ethylene oxide), poly(1,4-butadiene)-b-poly(methacrylic acid), poly(1,4-butadiene)-b-poly(vinyl alcohol), poly(dimethylsiloxane)-b-poly(acrylic acid), poly(dimethylsiloxane)-b-poly(ethylene oxide), poly(dimethylsiloxane)-b-poly(methacrylic acid), poly(dimethylsiloxane)-b-poly(n-butyl acrylate), poly(ethylene oxide)-b-poly(butadiene), poly(ethylene oxide)-b-poly(dimethylsiloxane), poly(ethylene oxide)-b-poly(meth poly(ethylene oxide)-b-poly(n-butyl acrylate), poly(ethylene oxide)-b-poly(styrene), poly(ethylene oxide)-b-poly(tert-butyl methacrylate), poly(methyl methacrylate)-b-poly(acrylic acid), poly(methyl methacrylate)-b-poly(dimethylsiloxane), poly(methyl methacrylate)-b-poly(ethylene oxide), poly(methyl methacrylate)-b-poly(methacrylic acid), poly(methyl methacrylate)-b-poly(styrene), poly(n-butyl acrylate)-b-poly(acrylic acid), poly(propylene oxide)-b-poly(butadiene), poly(propylene oxide)-b-poly(dimethylsiloxane), poly(propylene oxide)-b-poly(methyl methacrylate), poly(propylene oxide)-b-poly(n-butyl acrylate), poly(propylene oxide)-b-poly(styrene), poly(propylene oxide poly(vinyl alcohol)-b-poly(tert-butyl methacrylate), poly(vinyl alcohol)-b-poly(butadiene), poly(vinyl alcohol)-b-poly(dimethylsiloxane), poly(vinyl alcohol)-b-poly(methyl methacrylate), poly(vinyl alcohol)-b-poly(n-butyl acrylate), poly(vinyl alcohol)-b-poly(styrene), poly(vinyl alcohol)-b-poly(tert-butyl methacrylate), poly(1,2-butadiene), 15000 -b-Poly(acrylic acid) 6500 , poly(1,4-butadiene) 9000 -b-Poly(acrylic acid) 3500 , poly(dimethylsiloxane) 5000 -b-Poly(ethylene oxide) 2100, poly(dimethylsiloxane) 8000 -b-Poly(acrylic acid) 8000 , poly(methyl methacrylate) 3000 -b-Poly(ethylene oxide) 3000 , poly(methyl methacrylate) 7400 -b-Poly(acrylic acid) 24300 , poly(n-butyl acrylate) 7500 -b-Poly(acrylic acid) 5500 ,polystyrene) 1300 -b-Poly(ethylene oxide) 5600 , poly(vinyl alcohol) 2300 -b-Poly(methyl methacrylate) 25000 , poly(vinyl alcohol) 2500 -b-Poly(styrene) 12500 and combinations thereof.
[0042] In some embodiments, the amphiphilic block copolymer is a poly(1,2-butadiene)-based copolymer, a poly(1,2-butadiene-co-1,4-butadiene)-based copolymer, a poly(1,2-isoprene)-based copolymer, a poly(1,2-isoprene-co-1,4-isoprene)-based copolymer, a poly(1,4-butadiene)-based copolymer, a poly(1,4-butanediol diacrylate)-based copolymer, a poly(1,4-butanediol dimethacrylate)-based copolymer, a poly(1,4-isoprene)-based copolymer, a poly(2-acrylamide)-based copolymer, -2-methylpropanesulfonic acid sodium salt) based copolymers, poly(2-acrylamido-2-methylpropanesulfonic acid) based copolymers, poly(2-ethyloxazoline) based copolymers, poly(2-ethylhexyl acrylate) based copolymers, poly(2-hydroxyethyl methacrylate) based copolymers, poly(2-methoxyethyl acrylate) based copolymers, poly(2-methyloxazoline) based copolymers, poly(2-vinylnaphthalene) based copolymers, poly(2-vinylpyridine) based copolymers, poly(4-chloromethylstyrene) based copolymers ) copolymers, poly(4-hydroxystyrene) copolymers, poly(4-styrenesulfonic acid sodium salt) copolymers, poly(4-styrenesulfonic acid) copolymers, poly(4-vinylbiphenyl) copolymers, poly(4-vinylpyridine) copolymers, poly(4-vinylbenzoic acid) copolymers, poly(4-vinylpyridine decyl iodide) copolymers, poly(acrylamide) copolymers, poly(acrylate) copolymers, poly(acrylic acid sodium salt) copolymers, poly(acrylic acid) copolymers, poly( acrylonitrile)-based copolymers, poly(adipic anhydride)-based copolymers, poly(alkyl acrylate)-based copolymers, poly(alkyl methacrylate)-based copolymers, poly(alkyl siloxane)-based copolymers, poly(alkyl acrylic acid)-based copolymers, poly(alkylene oxide)-based copolymers, poly(butylene oxide)-based copolymers, poly(cyclohexylethylene)-based copolymers, poly(dialkyl siloxane)-based copolymers, poly(diene)-based copolymers, poly(dimethyl siloxane)-based copolymers, poly(dimethyl siloxane,ω-silanol terminated) copolymers, poly(ethylene oxide diacrylate) copolymers, poly(ethylene oxide dimethacrylate) copolymers, poly(ethylene oxide) copolymers, poly(ethylene propylene) copolymers, poly(ethylene) copolymers, poly(ethylene-co-butylene) copolymers, poly(glycerol diacrylate) copolymers, poly(glycerol dimethacrylate) copolymers, poly(glycolide) copolymers, poly(isobutylene) copolymers, poly(lactide) copolymers, poly(methacrylate) copolymers, poly(methacrylic acid sodium salt) copolymers, poly(methacrylic acid) copolymers, poly(methyl acrylate) copolymers, poly(methyl methacrylate) copolymers, poly(methyleneindane) copolymers, poly(N,N-dimethylacrylamide) copolymers, poly(N,N-dimethylaminoethyl methacrylate)-based copolymers, poly(n-butyl acrylate)-based copolymers, poly(neopentyl 4-styrenesulfonate)-based copolymers, poly(neopentyl methacrylate)-based copolymers, poly(N-isopropylacrylamide)-based copolymers, poly(nitrobenzyl methacrylate)-based copolymers, poly(N-methyl 2-vinylpyridinium iodide)-based copolymers, poly(N-vinylimidazole)-based copolymers, poly(N-vinylpyrrolidone)-based copolymers, poly(olefin)-based copolymers, poly(propylene oxide diacrylate)-based copolymers, poly(propylene oxide dimethacrylate)-based copolymers, poly(propylene oxide)-based copolymers, poly(p-vinylbenzenesulfonic acid)-based copolymers, poly(siloxane)-based copolymers, poly(sodium styrenesulfonate)-based copolymers, poly(styrene)-based copolymers, poly(styrene-co-4-styrene)-based copolymers sulfonic acid sodium salt)-based copolymers, poly(styrene-co-4-styrenesulfonic acid)-based copolymers, poly(sulfonated glycidyl methacrylate)-based copolymers, poly(tert-butyl 4-vinylbenzoate)-based copolymers, poly(tert-butyl acrylate)-based copolymers, poly(tert-butyl methacrylate)-based copolymers, poly(tert-butyl methacrylate-co-n-butyl methacrylate)-based copolymers, poly(tetrahydrofurfuryl methacrylate)-based copolymers, poly(trimethylsiloxy-2-ethyl methacrylate)-based copolymers, poly(vinyl alcohol)-based copolymers, poly(vinylpyridine)-based copolymers, poly(α-methoxy-terminated)-based copolymers, poly(α-propylacrylic acid)-based copolymers, poly(ε-caprolactone)-based copolymers, substituted poly(styrene)-based copolymers, poly(methylhydrogensiloxane)-based copolymers, and combinations thereof.
[0043] In some embodiments, the amphiphilic block copolymer is end-functionalized, and optionally the amphiphilic block copolymer is acrylate-terminated, alkyl acrylate-terminated, methacrylate-terminated, alkyl methacrylate-terminated, or a combination thereof.
[0044] In some embodiments, the number average molecular weight (M n ) are independently from about 1,300 to about 32,500, from about 250 to about 10,000, or from 2,000 to about 8,000.
[0045] In some embodiments, the M of the hydrophobic block of the amphiphilic block copolymer n M of the hydrophilic block n is about 0.02 to about 128, about 0.05 to about 20, about 0.23 to about 10.9, or about 0.33 to about 3.
[0046] In some embodiments, the amphiphilic block copolymer is poly(ethylene glycol)-b-poly(styrene). In some embodiments, the number average molecular weight (M n ) is from about 500 to about 2000. In some embodiments, the number average molecular weight (M n ) is about 2,500 to about 10,000.
[0047] In some embodiments, the M of the poly(styrene) block to the poly(ethylene glycol) block in poly(ethylene glycol)-b-poly(styrene) n is about 2 to about 5, optionally about 2.5 to about 4.5 or about 3 to about 4.
[0048] In some embodiments, the amphiphilic block copolymer is selected from PS(1500)-PEO(6200), PEG5000-PS1600, PS(1300)-PEO(5600), and combinations thereof. Those skilled in the art will appreciate that the term "polyethylene oxide" and the abbreviation "PEO" refer to a polyether compound having the same general chemical structure as polyethylene glycol (PEG).
[0049] In some embodiments, the amphiphilic block copolymer included in the composite particle is crosslinked. In some embodiments, the amphiphilic block copolymer is crosslinked using a crosslinking method selected from dialdehyde crosslinking, diamine crosslinking, diol crosslinking, ester crosslinking, free radical initiated alkene polymerization, Q-ammonium crosslinking, silane crosslinking, trialdehyde crosslinking, triamine crosslinking, triol crosslinking, urethane crosslinking, and combinations thereof.
[0050] In some embodiments, the silane crosslinking is performed with a silane selected from monoalkyl silicates, dialkyl silicates, trialkyl silicates, tetraalkoxy orthosilicates, fumed silica, and combinations thereof. In some embodiments, the tetraalkoxy silicates are selected from tetramethyl orthosilicate (TMOS), tetraethyl orthosilicate (TEOS), and combinations thereof.
[0051] In some embodiments, the free radical initiated alkene polymerization is initiated with a thermally and / or photoactivated free radical initiator, optionally the free radical initiator is selected from a nitrile based initiator, a peroxide based initiator, and combinations thereof. In some embodiments, the free radical initiator is selected from azobisisobutyronitrile (AIBN), diisopropyl peroxydicarbonate (IPP), benzoyl peroxide (BPO), 1-hydroxycyclohexyl phenyl ketone, 2-hydroxy-2-methylpropiophenone, trimethylpropane tri(3-mercaptopropionate), and combinations thereof.
[0052] In some embodiments, the amphiphilic block copolymers included in the composite particles of the present disclosure can be crosslinked using two or more crosslinking methods. In some embodiments, the amphiphilic block copolymers are crosslinked using silane crosslinking and free radical initiated alkene polymerization crosslinking. In some embodiments, the amphiphilic block copolymers are crosslinked using TEOS and AIBN.
[0053] In some embodiments, the amphiphilic block copolymer is selected from the group consisting of poly(1,2-butadiene)-b-poly(acrylic acid) crosslinked with AIBN, poly(1,2-butadiene)-b-poly(acrylic acid) crosslinked with fumed silica, poly(1,2-butadiene)-b-poly(acrylic acid) crosslinked with TEOS, poly(1,2-butadiene)-b-poly(acrylic acid) crosslinked with TEOS and AIBN, poly(1,4-butadiene)-b-poly(acrylic acid) crosslinked with AIBN, poly(1,4-butadiene)-b-poly(acrylic acid) crosslinked with TEOS, poly(1,4-butadiene)-b-poly(acrylic acid) crosslinked with TEOS and AIBN, poly(dimethylsiloxane)-b-poly( acrylic acid), poly(dimethylsiloxane)-b-poly(ethylene oxide) crosslinked with TEOS, poly(methyl methacrylate)-b-poly(acrylic acid) crosslinked with TEOS, poly(methyl methacrylate)-b-poly(ethylene oxide) crosslinked with TEOS, non-crosslinked poly(methyl methacrylate)-b-poly(ethylene oxide), poly(n-butyl acrylate)-b-poly(acrylic acid) crosslinked with TEOS, poly(styrene)-b-poly(ethylene oxide) crosslinked with TEOS, poly(vinyl alcohol)-b-poly(methyl methacrylate) crosslinked with TEOS, poly(vinyl alcohol)-b-poly(styrene) crosslinked with TEOS, poly(1,2-butadiene) crosslinked with AIBN 15000 -b-Poly(acrylic acid) 6500 , poly(1,2-butadiene) crosslinked with fumed silica 15000 -b-Poly(acrylic acid) 6500 , poly(1,2-butadiene) crosslinked with TEOS 15000 -b-Poly(acrylic acid) 6500 , poly(1,2-butadiene) crosslinked with TEOS and AIBN 15000 -b-Poly(acrylic acid) 6500 , poly(1,4-butadiene) crosslinked with AIBN 9000 -b-Poly(acrylic acid) 3500 , poly(1,4-butadiene) crosslinked with TEOS9000 -b-Poly(acrylic acid) 3500 , poly(1,4-butadiene) crosslinked with TEOS and AIBN 9000 -b-Poly(acrylic acid) 3500 , poly(dimethylsiloxane) crosslinked with TEOS 5000 -b-Poly(ethylene oxide) 2100 , poly(dimethylsiloxane) crosslinked with TEOS 8000 -b-Poly(acrylic acid) 8000 , poly(methyl methacrylate) crosslinked with TEOS 3000 -b-Poly(ethylene oxide) 3000 , non-crosslinked poly(methyl methacrylate) 3000 -b-Poly(ethylene oxide) 3000 , poly(methyl methacrylate) crosslinked with TEOS 7400 -b-Poly(acrylic acid) 24300 , poly(n-butyl acrylate) crosslinked with TEOS 7500 -b-Poly(acrylic acid) 5500 , poly(styrene) crosslinked with TEOS 1300 -b-Poly(ethylene oxide) 5600 , poly(vinyl alcohol) crosslinked with TEOS 2300 -b-Poly(methyl methacrylate) 25000 , poly(vinyl alcohol) crosslinked with TEOS 2500 -b-Poly(styrene) 12500 and combinations thereof.
[0054] In some embodiments, the amphiphilic block copolymer is selected from the group consisting of uncrosslinked poly(methyl methacrylate)-b-poly(ethylene oxide), poly(dimethylsiloxane)-b-poly(poly(acrylic acid) crosslinked with TEOS, poly(methyl methacrylate)-b-poly(acrylic acid) crosslinked with TEOS, poly(1,2-butadiene)-b-poly(acrylic acid) crosslinked with TEOS, poly(1,4-butadiene)-b-poly(acrylic acid) crosslinked with TEOS, poly(dimethylsiloxane)-b-poly(ethylene oxide) crosslinked with TEOS, poly(vinyl alcohol)-b-poly(ethylene oxide) crosslinked with TEOS, and optionally the amphiphilic block copolymer is selected from poly(styrene)-b-poly(ethylene oxide) crosslinked with TEOS, poly(n-butyl acrylate)-b-poly(acrylic acid) crosslinked with TEOS, poly(1,2-butadiene)-b-poly(acrylic acid) crosslinked with AIBN, poly(1,4-butadiene)-b-poly(acrylic acid) crosslinked with AIBN, poly(1,2-butadiene)-b-poly(acrylic acid) crosslinked with TEOS and AIBN, poly(1,4-butadiene)-b-poly(acrylic acid) crosslinked with TEOS and AIBN, and combinations thereof; and optionally the amphiphilic block copolymer is selected from non-crosslinked poly(methyl methacrylate) 3000 -b-Poly(ethylene oxide) 3000 , poly(methyl methacrylate) crosslinked with TEOS 3000 -b-Poly(ethylene oxide) 3000 , poly(dimethylsiloxane) crosslinked with TEOS 8000 -b-Poly(acrylic acid) 8000 , poly(methyl methacrylate) crosslinked with TEOS 7400 -b-Poly(acrylic acid) 24300 , poly(1,2-butadiene) crosslinked with TEOS 15000 -b-Poly(acrylic acid) 6500 , poly(1,4-butadiene) crosslinked with TEOS 9000 -b-Poly(acrylic acid) 3500 , poly(dimethylsiloxane) crosslinked with TEOS 5000 -b-Poly(ethylene oxide) 2100, poly(vinyl alcohol) crosslinked with TEOS 2300 -b-Poly(ethylene oxide) 2100 , poly(styrene) crosslinked with TEOS 1300 -b-Poly(ethylene oxide) 5600 , poly(n-butyl acrylate) crosslinked with TEOS 7500 -b-Poly(acrylic acid) 5500 , poly(1,2-butadiene) crosslinked with AIBN 15000 -b-Poly(acrylic acid) 6500 , poly(1,4-butadiene) crosslinked with AIBN 9000 -b-Poly(acrylic acid) 3500 , poly(1,2-butadiene) crosslinked with TEOS and AIBN 15000 -b-Poly(acrylic acid) 6500 , poly(1,4-butadiene) crosslinked with TEOS and AIBN 9000 -b-Poly(acrylic acid) 3500 and combinations thereof.
[0055] When the composite particles are used in contact lenses, the amphiphilic block copolymer can be a biocompatible amphiphilic block copolymer. Such amphiphilic block copolymers are known to those skilled in the art. For example, such amphiphilic block copolymers are suitable for contacting the eye of a subject.
[0056] In some embodiments, the composite particles have diameters in the nanometer to micrometer range. In one embodiment, the composite particles have diameters in the micrometer range. In another embodiment, the composite particles have diameters in the nanometer range. In some embodiments, the composite particles have diameters from about 1 nm to about 600 nm. In some embodiments, the composite particles have diameters from about 30 nm to about 100 nm. In some embodiments, the composite particles have diameters from about 40 nm to about 60 nm. In some embodiments, the composite particles have diameters of about 50 nm. In some embodiments, the composite particles of the present disclosure have diameters of about 50 to about 400 nanometers. In some embodiments, the composite particles have diameters of about 90 to about 200 nanometers.
[0057] In some embodiments, the composite particles of the present disclosure include two or more hydrophobic dyes. In some embodiments, the composite particles of the present disclosure include two or more amphiphilic block copolymers.
[0058] In some embodiments, the amphiphilic block copolymer encapsulates the dye upon micelle formation.
[0059] In some embodiments, the composite particles are substantially solvent-free.
[0060] The composite particles of the present disclosure have been shown to be able to withstand certain conditions used in the manufacture of hydrogels, silicone hydrogels, and / or contact lenses.
[0061] In some embodiments, the composite particles have a power output of 12.8 mW / cm 2 The UV-Vis absorbance spectrum is essentially unchanged after 30 minutes of UV exposure at 50°C.
[0062] In some embodiments, 12.8 mW / cm 2 The maximum UV-Vis absorbance of the composite particles after 30 min of UV exposure at 12.8 mW / cm 2The absorbance of the sample is at least 50%, 60%, 70%, 80%, or 90% of the maximum UV-Vis absorbance before UV exposure at .
[0063] In some embodiments, the UV-Vis spectrum of the composite particle is 12.8 mW / cm 2 The compound is substantially unchanged after photobleaching following UV exposure at 250 nm for about 1 minute, about 3 minutes, about 5 minutes, about 10 minutes, or about 15 minutes.
[0064] In some embodiments, the maximum UV-Vis absorbance of the composite particles after UV photobleaching at 1 minute, about 3 minutes, about 5 minutes, about 10 minutes, or about 15 minutes is 12.8 mW / cm 2 at least 50%, 60%, 70%, 80%, or 90% of the maximum UV-Vis absorbance before UV exposure at 250 nm.
[0065] In some embodiments, the change in UV-Vis transmittance spectrum of the composite particle is 12.8 mW / cm 2 after photobleaching by UV exposure at 250 nm for 1 minute, about 3 minutes, about 5 minutes, about 10 minutes, or about 15 minutes, the percent change is less than 80%, less than 70%, less than 60%, less than 50%, or less than 40%.
[0066] In some embodiments, the maximum UV-Vis absorbance of the composite particles in water, THF, or a mixture thereof after heating at about 60° C., about 70° C., about 80° C., about 90° C., or about 100° C. for about 1 hour, about 3 hours, about 5 hours, about 8 hours, about 10 hours, about 12 hours, about 18 hours, about 24 hours, or about 30 hours is at least 50%, 60%, 70%, 80%, or 90% of the maximum UV-Vis absorbance before heating.
[0067] In some embodiments, the UV-Vis absorbance spectrum of the composite particles is substantially unchanged after autoclaving at about 121° C. at 108 kPa in aqueous solution.
[0068] In some embodiments, the maximum UV-Vis absorbance of the composite particles after autoclaving in aqueous solution at about 121° C. and 108 kPa is at least 50%, 60%, 70%, 80%, or 90% of the maximum UV-Vis absorbance before autoclaving.
[0069] In some embodiments, the UV-Vis absorbance spectrum of the composite particles after an ethanol wash with about 25% v / v, about 50% v / v, about 75% v / v, or about 95% v / v ethanol in water for about 1 hour is substantially unchanged.
[0070] In some embodiments, the maximum UV-Vis absorbance spectrum of the composite particles after an ethanol wash with about 25% v / v, about 50% v / v, about 75% v / v or about 95% v / v ethanol in water for about 1 hour is at least 50%, 60%, 70%, 80%, or 90% of the maximum UV-Vis absorbance spectrum before the ethanol wash.
[0071] In some embodiments, the composite particles are storage stable in saline at 50° C. for at least 1 day, at least 3 days, at least 4 days, at least 5 days, at least 125 hours, at least 130 hours, or at least 136 hours.
[0072] In some embodiments, the UV-Vis absorbance spectrum of the composite particles is substantially unchanged after storage in saline at 50° C. for at least 1 day, at least 3 days, at least 4 days, at least 5 days, at least 125 hours, at least 130 hours, or at least 136 hours.
[0073] In some embodiments, the maximum UV-Vis absorbance of the composite particles after storage in saline at 50° C. for at least 1 day, at least 3 days, at least 4 days, at least 5 days, at least 125 hours, at least 130 hours, or at least 136 hours is at least 50%, 60%, 70%, 80%, or 90% of the maximum UV-Vis absorbance before storage.
[0074] In some embodiments, 12.8 mW / cm 2 The change in maximum UV-Vis absorbance of the composite particles after photobleaching after about 1 minute, about 3 minutes, about 5 minutes, about 10 minutes, or about 15 minutes of UV exposure at 250 nm is less than the change in maximum UV-Vis absorbance of the hydrophobic dye alone after photobleaching after about 1 minute, about 3 minutes, about 5 minutes, about 10 minutes, or about 15 minutes of UV exposure at 250 nm.
[0075] In some embodiments, 12.8 mW / cm 2 The change in maximum UV-Vis transmittance of the composite particles after photobleaching after about 1 minute, about 3 minutes, about 5 minutes, about 10 minutes, or about 15 minutes of UV exposure at 250 nm is less than the change in maximum UV-Vis transmittance of the hydrophobic dye alone after photobleaching after about 1 minute, about 3 minutes, about 5 minutes, about 10 minutes, or about 15 minutes of UV exposure at 250 nm, respectively.
[0076] In some embodiments, the change in maximum UV-Vis absorbance of the composite particles after heating at about 60°C, about 70°C, about 80°C, about 90°C, or about 100°C for about 1 hour, about 3 hours, about 5 hours, about 8 hours, about 10 hours, about 12 hours, or about 18 hours is less than the change in maximum UV-Vis absorbance of the hydrophobic dye after heating at about 60°C, about 70°C, about 80°C, about 90°C, or about 100°C for about 1 hour, about 3 hours, about 5 hours, about 8 hours, about 10 hours, about 12 hours, or about 18 hours, respectively.
[0077] In some embodiments, the change in maximum UV-Vis absorbance of the composite particles after autoclaving at about 121° C. at 108 kPa in aqueous solution is less than the change in maximum UV-Vis absorbance of the hydrophobic dye after autoclaving at about 121° C. at 108 kPa in aqueous solution.
[0078] In some embodiments, the change in maximum UV-Vis absorbance of the composite particles after storage in saline at 50°C for at least 1 day, at least 3 days, at least 4 days, at least 5 days, at least 125 hours, at least 130 hours, or at least 136 hours is less than the change in maximum UV-Vis absorbance of the hydrophobic dye after storage in saline at 50°C for at least 1 day, at least 3 days, at least 4 days, at least 5 days, at least 125 hours, at least 130 hours, or at least 136 hours, respectively.
[0079] In some embodiments, the hydrophobic dye has absorbance in a region selected from the ultraviolet region, the visible region, and combinations thereof. In one embodiment, the hydrophobic dye has absorbance in the ultraviolet region. In another embodiment, the hydrophobic dye has absorbance in the visible region. In another embodiment, the hydrophobic dye has absorbance in the ultraviolet and visible regions.
[0080] In another aspect, the present disclosure includes a composition comprising one or more composite particles of the present disclosure in a solvent selected from an aqueous solvent, an organic solvent, and mixtures thereof. The present disclosure also includes a composition comprising one or more composite particles of the present disclosure in a solvent selected from an aqueous solvent, an organic solvent, and mixtures thereof. Composite particles in an aqueous medium, comprising: A hydrophobic dye; Hydrophobic dye-encapsulated amphiphilic block copolymers and wherein the hydrophobic dye has an absorbance ranging from the ultraviolet to the infrared region of the electromagnetic spectrum. The composition includes:
[0081] It will be understood by those skilled in the art that the composite particles in the compositions of the present disclosure can vary as can the embodiments of the composite particles of the present disclosure.
[0082] In some embodiments, the solvent is an aqueous solvent, hi some embodiments, the solvent is water.
[0083] In some embodiments, the organic solvent is water miscible, hi some embodiments, the organic solvent is selected from alcohols, ethers, ketones, amides, amines, thiols, aldehydes, carboxylic acids, butanediols, ethanolamines, dimethoxyethane, dimethylsulfoxide, dioxanes, alkylamines, pyrrolidones, propanediols, pyridines, and combinations thereof.
[0084] In some embodiments, the organic solvent is selected from ethanol, methanol, propanol, butanol, butoxyethanol, THF, tetrahydropyran (THP), dioxane, DMF, acetone, acetonitrile, N,N-dimethylformamide, dioxane, methyl ethyl ketone, acetaldehyde, 1,2-butanediol, 1,3-butanediol, 1,4-butanediol, diethanolamine, diethylenetriamine, dimethoxyethane, ethylamine, methylamine, N-methyl-2-pyrrolidone, 1-propanol, 1,3-propanediol, pyridine, and combinations thereof.
[0085] In some embodiments, the compositions of the present disclosure have a luminance of 12.8 mW / cm 2 The UV-Vis absorbance spectrum is essentially unchanged after 30 minutes of UV exposure at 50°C.
[0086] In some embodiments, the compositions of the present disclosure are stable in tetrahydrofuran (THF), water, or mixtures thereof for at least 1 day, 1 week, 3 weeks, 7 weeks, 11 weeks, 3 months, or 6 months. In some embodiments, the compositions of the present disclosure are stable in THF for at least 1 day, 1 week, 3 weeks, 7 weeks, or 11 weeks. In some embodiments, the compositions of the present disclosure are stable in THF for at least 6 months.
[0087] In some embodiments, the maximum UV-Vis absorbance of a composition of the present disclosure after heating in water, aqueous THF, or mixtures thereof for 15 minutes at about 60° C., about 70° C., about 80° C., about 90° C., or about 100° C. is at least 50%, 60%, 70%, 80%, or 90% of the maximum UV-Vis absorbance before heating. In some embodiments, the UV-Vis absorbance of a composite particle composition of the present disclosure does not change substantially over 3 months of storage at standard room temperature.
[0088] In some embodiments, 12.8 mW / cm 2 The maximum UV-Vis absorbance of the composition after 30 minutes of UV exposure at 12.8 mW / cm 2 The absorbance of the sample is at least 50%, 60%, 70%, 80%, or 90% of the maximum UV-Vis absorbance before UV exposure at .
[0089] In some embodiments, the UV-Vis spectrum of the composite particle is 12.8 mW / cm 2 The antibody is substantially unchanged after photobleaching following UV exposure at 250 nm for 1 minute, about 3 minutes, about 5 minutes, about 10 minutes, or about 15 minutes.
[0090] In some embodiments, the maximum UV-Vis absorbance of the composition after photobleaching by UV exposure at 250 nm for about 1 minute, about 3 minutes, about 5 minutes, about 10 minutes, or about 15 minutes is 12.8 mW / cm 2 at least 50%, 60%, 70%, 80%, or 90% of the maximum UV-Vis absorbance before UV exposure at 250 nm.
[0091] In some embodiments, the change in the UV-Vis transmittance spectrum of the composition is less than 12.8 mW / cm 2 after photobleaching by UV exposure at 250 nm for about 1 minute, about 3 minutes, about 5 minutes, about 10 minutes, or about 15 minutes, the percent change is less than 80%, less than 70%, less than 60%, less than 50%, or less than 40%.
[0092] In some embodiments, the maximum UV-Vis absorbance of the composition in water, THF, or a mixture thereof after heating at about 60° C., about 70° C., about 80° C., about 90° C., or about 100° C. for about 1 hour, about 3 hours, about 5 hours, about 8 hours, about 10 hours, about 12 hours, about 18 hours, about 24 hours, or about 30 hours is at least 50%, 60%, 70%, 80%, or 90% of the maximum UV-Vis absorbance before heating.
[0093] In some embodiments, the UV-Vis absorbance spectrum of the composition is substantially unchanged after autoclaving at about 121° C. at 108 kPa in aqueous solution.
[0094] In some embodiments, the maximum UV-Vis absorbance of the composition after autoclaving in aqueous solution at about 121° C. and 108 kPa is at least 50%, 60%, 70%, 80%, or 90% of the maximum UV-Vis absorbance before autoclaving.
[0095] In some embodiments, the UV-Vis absorbance spectrum of the composition after an ethanol wash with about 25% v / v, about 50% v / v, about 75% v / v, or about 95% v / v ethanol in water for about 1 hour is substantially unchanged.
[0096] In some embodiments, the maximum UV-Vis absorbance spectrum of the composition after an ethanol wash with about 25% v / v, about 50% v / v, about 75% v / v, or about 95% v / v ethanol in water for about 1 hour is at least 50%, 60%, 70%, 80%, or 90% of the maximum UV-Vis absorbance spectrum before the ethanol wash.
[0097] In some embodiments, the composition is storage stable in saline at 50° C. for at least 1 day, at least 3 days, at least 4 days, at least 5 days, at least 125 hours, at least 130 hours, or at least 136 hours.
[0098] In some embodiments, the UV-Vis absorbance spectrum of the composition is substantially unchanged after storage in saline at 50° C. for at least 1 day, at least 3 days, at least 4 days, at least 5 days, at least 125 hours, at least 130 hours, or at least 136 hours.
[0099] In some embodiments, the maximum UV-Vis absorbance of the composition after storage in saline at 50° C. for at least 1 day, at least 3 days, at least 4 days, at least 5 days, at least 125 hours, at least 130 hours, or at least 136 hours is at least 50%, 60%, 70%, 80%, or 90% of the maximum UV-Vis absorbance before storage.
[0100] In some embodiments, the compositions are stable in aqueous tetrahydrofuran (THF), water, or a mixture thereof for at least 1 day, at least 1 week, at least 3 weeks, at least 7 weeks, at least 11 weeks, at least 3 months, or at least 6 months.
[0101] In some embodiments, the composition is stable in aqueous THF for at least 1 day, 1 week, 3 weeks, 7 weeks, or 11 weeks, and the composition is stable in THF for at least 6 months.
[0102] In some embodiments, the compositions of the present disclosure have a FWHM of less than 150 nm. In some embodiments, the FWHM of the composition is less than twice the FWHM of the dye.
[0103] In some embodiments, the compositions of the present disclosure are prepared by a method comprising preparing a dye / polymer solution comprising a hydrophobic dye and an amphiphilic block copolymer in an organic solvent, and adding the dye / polymer solution to water to obtain the composition as an aqueous micellar solution. In some embodiments, the addition of the dye / polymer solution to water or the combination of the dye / polymer solution with water is performed by using a process comprising flash nanoprecipitation (or an equivalent encapsulation technique), microfluidic mixing, ultrasonication, sonication, mechanical stirring, a syringe pump, or a Pasteur pipette. In another embodiment, the process comprises flash nanoprecipitation. In some embodiments, the water is stirred or mixed during the addition. In some embodiments, the process further comprises centrifuging the aqueous micellar solution to contain a supernatant comprising the composition.
[0104] In some embodiments, the composition of the present disclosure is prepared by a method comprising preparing a dye / polymer solution comprising a hydrophobic dye and an amphiphilic block copolymer in an organic solvent, combining the dye / polymer solution with water, and mixing the dye / polymer solution with water to obtain the composition as an aqueous micellar solution. In some embodiments, the combination of the dye / polymer solution with water and the mixing of the dye / polymer solution with water are performed by using a process comprising flash nanoprecipitation (or equivalent encapsulation techniques), microfluidic mixing, ultrasonication, sonication, mechanical stirring, syringe pumps, or Pasteur pipettes. In another embodiment, the process comprises flash nanoprecipitation. In some embodiments, the process further comprises centrifuging the aqueous micellar solution to contain a supernatant comprising the composition.
[0105] Thus, in another aspect, the present disclosure also includes a method of preparing a composition of the present disclosure, comprising preparing a dye / polymer solution comprising a hydrophobic dye and an amphiphilic block copolymer in an organic solvent, and adding the dye / polymer solution to water to obtain the composition as an aqueous micellar solution. In some embodiments, the addition of the dye / polymer solution to the water is performed by using a process comprising flash nanoprecipitation (or equivalent encapsulation technique), microfluidic mixing, ultrasonication, sonication, mechanical stirring, a syringe pump, or a Pasteur pipette. In another embodiment, the process comprises flash nanoprecipitation. In some embodiments, the water is stirred or mixed during the addition. In some embodiments, the method further comprises centrifuging the aqueous micellar solution to obtain a supernatant comprising the composition.
[0106] In another aspect, the present disclosure also includes a method of preparing a composition of the present disclosure, comprising preparing a dye / polymer solution comprising a hydrophobic dye and an amphiphilic block copolymer in an organic solvent, combining the dye / polymer solution with water, and mixing the dye / polymer solution with water to obtain the composition as an aqueous micellar solution. In some embodiments, the combination and mixing of the dye / polymer solution with water is performed by using a process comprising flash nanoprecipitation (or equivalent encapsulation technique), microfluidic mixing, ultrasonication, sonication, mechanical stirring, syringe pumps, or Pasteur pipettes. In another embodiment, the process comprises flash nanoprecipitation. In some embodiments, the method further comprises centrifuging the aqueous micellar solution to obtain a supernatant comprising the composition.
[0107] Further, the present disclosure includes a method of preparing the composite particles of the present disclosure, comprising the steps of preparing a dye / polymer solution comprising a hydrophobic dye and an amphiphilic block copolymer in an organic solvent; adding the dye / polymer solution to water with mixing to obtain the composite particles in an aqueous solution; and optionally obtaining the composite particles from the aqueous solution by filtration.
[0108] In another aspect, the present disclosure includes a method of preparing the composite particles of the present disclosure, comprising the steps of: preparing a dye / polymer solution comprising a hydrophobic dye and an amphiphilic block copolymer in an organic solvent; combining the dye / polymer solution with water, and mixing the dye / polymer solution with the water to obtain the composite particles in an aqueous solution; and optionally obtaining the composite particles from the aqueous solution by filtration.
[0109] In some embodiments, the composite particles of the present disclosure comprise an amphiphilic block copolymer that is crosslinked using one or more crosslinking agents. Those skilled in the art can understand that the crosslinking of the amphiphilic polymer can be carried out using any suitable method known in the art. In one aspect, the present disclosure also comprises a method of preparing a composition comprising the composite particles of the present disclosure, comprising the steps of: preparing a dye / polymer / crosslinking agent solution comprising a hydrophobic dye, an amphiphilic block copolymer and one or more crosslinking agents in an organic solvent; and adding the dye / polymer / crosslinking agent solution to water while mixing to obtain an aqueous micellar solution.
[0110] In another aspect, the present disclosure also includes a method of preparing a composition comprising the composite particles of the present disclosure, comprising the steps of: preparing a dye / polymer / crosslinker solution comprising a hydrophobic dye, an amphiphilic block copolymer and one or more crosslinkers in an organic solvent; combining the dye / polymer / crosslinker solution with water; and mixing the dye / polymer / crosslinker solution with water to obtain an aqueous micellar solution.
[0111] In another aspect, the present disclosure includes a method of preparing a composite particle of the present disclosure, comprising the steps of: preparing a dye / polymer / crosslinker solution comprising a hydrophobic dye, an amphiphilic block copolymer, and a crosslinker in an organic solvent; adding the dye / polymer / crosslinker solution to water with mixing to obtain an aqueous solution; and optionally obtaining the composite particle from the aqueous solution by filtration.
[0112] In another aspect, the present disclosure includes a method of preparing a composite particle of the present disclosure, comprising the steps of: preparing a dye / polymer / crosslinker solution comprising a hydrophobic dye, an amphiphilic block copolymer, and a crosslinker in an organic solvent; combining the dye / polymer / crosslinker solution with water; mixing the dye / polymer / crosslinker solution with water to obtain an aqueous solution; and optionally obtaining the composite particle from the aqueous solution by filtration.
[0113] In some embodiments, the crosslinking agent is selected from silanes as defined above, thermally and / or photoactivated free radical initiators as defined above, and combinations thereof. In some embodiments, the crosslinking agent is selected from silanes and combinations thereof as defined above, and the method optionally includes heating the aqueous micellar or water solution. In some embodiments, the crosslinking is initiated by heating. In some embodiments, the crosslinking agent is selected from thermally and / or photoactivated free radical initiators, and the method includes heating and / or UV irradiating the aqueous micellar or water solution. In some embodiments, the crosslinking agent is one or more silanes and one or more free radical initiators as defined above, and the method includes heating and / or UV irradiating the aqueous micellar or water solution. In some embodiments, the heating and / or UV irradiating initiates the free radical process that leads to alkene polymerization crosslinking.
[0114] In some embodiments, the composite particles of the present disclosure further comprise a cryoprotectant. In some embodiments, the cryoprotectant is PEG4000. In some embodiments, the method for preparing the composition or composite particles of the present disclosure further comprises adding a cryoprotectant to the aqueous solution or aqueous micellar solution, and drying the aqueous solution or aqueous micellar solution to obtain dry composite particles. For example, drying can be performed by freeze-drying or suction filtration.
[0115] In some embodiments, the organic solvent used in the preparation method of the composition of the present disclosure is selected from THF, dichloromethane, chloroform, N,N-dimethylformamide, dioxane, methanol, ethanol, propanol or other suitable alcohol, ethylene glycol, glycerol, diethyl ether, diisopropyl ether, methyl ethyl ketone, dichlorooxyethane, xylene, acetone, benzene, toluene, and combinations thereof. In some embodiments, the organic solvent is THF.
[0116] In some embodiments, the compositions of the present disclosure exhibit stability in organic solvents such as THF and aqueous solvents such as water, as well as at various elevated temperatures, such that the compositions of the present disclosure may be suitable for manufacturing processes involving different conditions, such as different solvents and different temperatures. Thus, in some embodiments, the composite particles and / or compositions of the present disclosure may be used as optical filters in hydrogels, such as silicone hydrogels. For example, as optical filters in contact lenses, where the contact lenses are optionally hydrogel or silicone hydrogel based.
[0117] Thus, in another aspect, the present disclosure includes contact lenses comprising one or more composite particles or one or more compositions of the present disclosure.
[0118] In some embodiments, the contact lenses are hydrogel or silicone hydrogel based.
[0119] In some embodiments, the hydrogel or silicone hydrogel is biocompatible and / or suitable for use in an animal subject; optionally, the animal subject is a mammal; optionally, the mammal is a human.
[0120] In some embodiments, 12.8 mW / cm for about 1 minute, about 3 minutes, about 5 minutes, about 10 minutes, or about 15 minutes. 2 The maximum UV-Vis absorbance of contact lenses after photobleaching with 250 nm UV exposure is 12.8 mW / cm2 at least 50%, 60%, 70%, 80%, or 90% of the maximum UV-Vis absorbance before UV exposure at 250 nm.
[0121] In some embodiments, the change in the UV-Vis transmittance spectrum of the contact lens is less than 12.8 mW / cm 2 after photobleaching by UV exposure at 250 nm for about 1 minute, about 3 minutes, about 5 minutes, about 10 minutes, or about 15 minutes, the percent change is less than 80%, less than 70%, less than 60%, less than 50%, or less than 40%.
[0122] In some embodiments, the UV-Vis absorbance spectrum of the contact lens is substantially unchanged after autoclaving in aqueous solution at about 121° C. and 108 kPa.
[0123] In some embodiments, the UV-Vis absorbance spectrum of a contact lens after an ethanol wash in about 25% v / v, about 50% v / v, about 75% v / v or about 95% v / v ethanol in water for about 1 hour is substantially unchanged.
[0124] In some embodiments, the maximum UV-Vis absorbance spectrum of the contact lens after an ethanol wash with about 25% v / v, about 50% v / v, about 75% v / v or about 95% v / v ethanol in water for about 1 hour is at least 50%, 60%, 70%, 80%, or 90% of the maximum UV-Vis absorbance spectrum before the ethanol wash.
[0125] In some embodiments, the contact lenses are storage stable in saline at 50° C. for at least 1 day, at least 3 days, at least 4 days, at least 5 days, at least 125 hours, at least 130 hours, or at least 136 hours.
[0126] In some embodiments, the UV-Vis absorbance spectrum of the contact lens is substantially unchanged after storage in saline at 50° C. for at least 1 day, at least 3 days, at least 4 days, at least 5 days, at least 125 hours, at least 130 hours, or at least 136 hours.
[0127] In some embodiments, the maximum UV-Vis absorbance of the contact lens after storage in saline at 50° C. for at least 1 day, at least 3 days, at least 4 days, at least 5 days, at least 125 hours, at least 130 hours, or at least 136 hours is at least 50%, 60%, 70%, 80%, or 90% of the maximum UV-Vis absorbance before storage.
[0128] In some embodiments, the hydrophobic dye is non-reactive to hydrogels or silicone hydrogels. For example, the term "non-reactive" as used herein may mean that the dye does not contain functional groups that can participate in the polymerization / crosslinking process that creates the hydrogel. For example, the non-reactive dye optionally does not contain vinyl or methacrylate groups.
[0129] Any suitable hydrogel polymer material can be used in the contact lenses of the present disclosure. For example, some common hydrogel materials can be prepared from suitable hydrophilic monomers, hydrophobic monomers, siloxane monomers, or combinations thereof, and optionally suitable crosslinking agents. In some embodiments, it is understood by those skilled in the art that the contact lenses are prepared from materials that are biocompatible or suitable for use in the eye of a subject. In some embodiments, the subject is an animal subject, for example, a human subject.
[0130] For example, hydrophilic monomers include methyl acrylate, ethyl acrylate, acrylic acid, methyl methacrylate, ethyl methacrylate, 2-hydroxyethyl methacrylate, methacrylic acid, 2,2,2-trifluoroethyl methacrylate, 2,2,3,3,3-pentafluoropropyl methacrylate, hexafluoroisopropyl methacrylate, 1,1,2,2-tetrafluoroethoxy 2-hydroxypropyl methacrylate, ethylene glycol dimethacrylate, tetraethylene glycol dimethacrylate, and diethylene glycol. Dimethacrylate, polyethylene glycol dimethacrylate, trimethylolpropane trimethacrylate, pentaerythritol tetramethacrylate, bisphenol A dimethacrylate, vinyl methacrylate triallyl trimellitate, and allyl methacrylate 2-methacryloylcarbamoyloxyethyl methacrylate, 2-2(2-methacryloxycarbamoyloxy)ethyl acrylate, 2-(2-methacryloxyethylcarbamoyloxy)propyl methacrylate, 2-methacryloxyethylcarbamoyloxytetraethylene Glycol methacrylate, methacryloyloxyethyl isocyanate, trifluoroethyl methacrylate, 1,1,2,2-tetraethoxy-2-hydroxypropyl methacrylate, 3-(1,1,2,2-tetrafluoroethoxy)-2-hydroxypropyl methacrylate, hydroxyethyl methacrylate, N-methyl-N-vinylacetamide, hydroxybutyl methacrylate, glycerol monomethacrylate, glycerol dimethacrylate, N-vinylformamide, N-vinyl-N-ethylformamide, N-vinylacetamide , N-vinylisopropylamide, N-vinyl-N-methylacetamide, N-vinyl-N-ethylacetamide, N-vinylpyrrolidone, N-vinylcaprolactam, N-vinyllactam, 1-vinylazonan-2-one, 2-hydroxypropyl methacrylate, 2-hydroxybutyl acrylate, 4-hydroxybutyl acrylate, glycerol methacrylate, itaconic acid, fumaric acid, maleic acid, dimethylaminoethyl methacrylate, diethylaminoethyl methacrylate, N,N-dimethylacrylamide, N,N-diethylacryl amides, N-methylacrylamide, methylenebisacrylamide, diacetone acrylamide, methoxyethylene glycol monomethacrylate, methoxypropylene glycol monoacrylate, acrylic acid fluoroalkyl esters, tetrafluoroethyl methacrylate, tetrafluoropropyl methacrylate, pentafluoropropyl methacrylate, trifluoroethyl acrylate, tetrafluoroethyl acrylate, tetrafluoropropyl acrylate, pentafluoropropyl acrylate, hexafluorobutyl acrylate, hexafluoroisopropyl acrylate, polyethylene glycols, ethoxylated alkyl glucosides, methacrylic anhydride, methacryloyl chloride, vinyl benzoyl chloride, and N-isopropylacrylamide.
[0131] For example, hydrophobic monomers include isobornyl methacrylate, methyl methacrylate, triallyl isocyanurate, allyl methacrylate, styrene, tert-butyl styrene, α-methyl styrene, t-butyl methacrylate, cyclohexyl methacrylate, alkyl methacrylates, fluorinated alkyl methacrylates, long chain acrylamides (e.g., octylacrylamide), cyclopentyl methacrylate, and perfluorocyclohexyl methacrylate.
[0132] For example, silicone hydrogels can be prepared from any one or more of the monomers listed above and also include one or more silicone components, such as fluorosilicone acrylates, and / or polyorganosiloxanes, such as polydimethylsiloxane (PDMS). For example, other siloxane monomers include tris(trimethylsiloxy)silylpropyl methacrylate, bis(trimethylsiloxy)methylsilylpropyl methacrylate, pentamethyldisiloxanepropyl methacrylate, tris(trimethylsiloxy)silylpropyloxyethyl methacrylate, tris(polydimethylsiloxy)silylpropyl methacrylate, tri(dimethyltrifluoropropylsiloxy)silylpropyl methacrylate, tetramethyldisiloxanebis(propyl methacrylate), 2-methacryloylcarbamoyloxyethyl methacrylate, 2-2(2-methacryloxycarbamoyloxy)ethyl acrylate, 2-(2-methacryloxyethylcarbamoyloxy)propyl methacrylate, 2-methacryloxyethylcarbamoyloxytetraethylene glycol methacrylate methacryloyloxyethyl isocyanate, poly(hydroxyethyl methacrylate), polydimethylsiloxane (PDMS), 1,3-bis(3 -methacryloxypropyl)tetramethyldisiloxane, octamethylcyclotetrasiloxane, 1,3,5-trimethyltrifluoropropyl-cyclotrisiloxane, 1,3,5,7-tetramethylcyclotetrasiloxane, 1,3-bis(3-(2-hydroxyethoxy)propyl)tetramethyldisiloxane, alpha-butyl-omega-3-(2-hydroxyethoxy)propyl)polydimethylsiloxane, tris(dimethyltrifluoropropylsiloxy)silylpropylmeth acrylate, pentamethyldisiloxanylmethyl methacrylate, tris(trimethylsiloxy)methacryloxypropyl silane, phenylthreitolmethyl-disiloxanylethyl acrylate, methyldi(trimethylsiloxy)methacryloxymethylsilane, 3-tris(trimethylsiloxy)silylpropyl vinyl carbamate, 3-tris(trimethylsiloxy)silylpropyl allyl carbamate, 3-tris(trimethylsiloxy)silylpropyl vinyl carbonate, methacryloxypropyl methyl silane, methyldi(trimethylsiloxy)methacryloxy ... Examples of suitable siloxanes include aryloxypropyl tris(trimethylsiloxy)silane, 3-methacryloxypropyl bis(trimethylsiloxy)methylsilane, and methacryloxypropyl pentamethyldisiloxane.
[0133] The preparation of the hydrogel material may also include the use of suitable crosslinkers, photoinitiators, thermal initiators, catalysts, and / or polymerization inhibitors.
[0134] For example, crosslinking agents include ethylene glycol dimethacrylate, diethylene glycol dimethacrylate, triethylene glycol dimethacrylate, polyethylene glycol dimethacrylate, trimethylolpropane trimethacrylate, pentaerythritol tetramethacrylate, bisphenol A dimethacrylate, vinyl methacrylate, allyl methacrylate, ethylene glycol diacrylate, diethylene glycol diacrylate, triethylene glycol diacrylate, polyethylene glycol diacrylate, trimethylolpropane triacrylate, pentaerythritol tetraacrylate, bisphenol A diacrylate, vinyl acrylate, and allyl acrylate.
[0135] For example, photoinitiators can include benzoinethyl ether, benzil dimethyl ketal, α,α-diethoxyacetophenone, and 2,4,6-trimethylbenzoyldiphenylphosphine oxide.
[0136] For example, thermal initiators can include benzoyl peroxide, t-butyl peroxide, azobisisobutyronitrile, and azobisdimethylvaleronitrile.
[0137] For example, the catalyst may include trifluoromethanesulfonic acid, sulfuric acid, and an acidic clay.
[0138] For example, polymerization inhibitors can include hydroquinone, 2,6-di-tert-butyl-4-methylphenol, and para-methoxyphenol.
[0139] In some embodiments, the composite particles and / or compositions of the present disclosure can be used to filter or block a range of wavelengths of optical radiation, such that different wavelengths can be selectively blocked by incorporating different dyes with different absorption characteristics and / or by using multiple composite particles or compositions of the present disclosure. Thus, in another aspect, the present disclosure includes a method of optical filtering comprising selectively blocking optical radiation using one or more composite particles or compositions of the present disclosure.
[0140] In another aspect, the present disclosure includes the use of one or more composite particles or compositions of the present disclosure as an optical filter. In some embodiments, the use of one or more composite particles or compositions of the present disclosure as an optical filter is in a contact lens. In some embodiments, the use of one or more composite particles or compositions of the present disclosure as an optical filter is in a hydrogel. In some embodiments, the optical filter is for selectively blocking optical radiation.
[0141] In some embodiments, the optical radiation that is selectively blocked is selected from infrared light, UV light, visible light, blue light, and combinations thereof. In some embodiments, the optical radiation that is selectively blocked is UV light or blue light. In one embodiment, the optical radiation that is selectively blocked is infrared light. In another embodiment, the optical radiation that is selectively blocked is UV light. In a further embodiment, the optical radiation that is selectively blocked is visible light, such as red light, blue light, or green light. In another embodiment, the optical radiation that is selectively blocked is blue light. In a further embodiment of the present disclosure, the optical radiation that is selectively blocked is a combination of infrared light, UV light, visible light, and / or blue light.
[0142] The following non-limiting examples are illustrative of the present disclosure. EXAMPLES
[0143] Example 1 General Methods and Materials The dyes Exciton® ABS 456 and 594 were purchased from Luxototica / Exciton (product numbers 04560, 05940). The block copolymer PS(1500)-PEO(6200) was purchased from Polymer Source Inc., product number P11112-SEO. Tetrahydrofuran (THF) used was purchased from Fisher Scientific (T397-4).
[0144] Spectrophotometer quartz cuvettes (VWR® Spectrophotometer Cells, Standard Rectangular) were purchased from VWR, catalog number 414004-064. The micropipettes used were Fisherbrand™ Finnpipette™ II adjustable volume pipettes, 100-1000 μL, Mandel PSR number 14440. UV-Vis spectra were acquired on an Agilent Cary™ 60 spectrophotometer. UV bleaching experiments were performed using a UV reactor, Rayonet Photochemical Reactor, model RPR-100, using ten 253.7 nm lamps and four 350 nm lamps with an intensity reading of 12,800 μW / cm. 2Dynamic light scattering (DLS) experiments were performed using a DLS instrument BI-200SM Research Goniometer System, serial number 80615 and a DLS detector BI-APDx DLS (Brookhaven Instruments), serial number 29244. The DLS instrument and detector were mounted on a TMC vibration controlled clean top (AMETEK Ultra Precision Technologies). The round bottom flask reaction block used was an Optitherm™ from Chemglass, Radleys Discovery Technologies, RR98072. The cooling tube used was a KIMBLE® 21800KIMAX®.
[0145] Example 2 Encapsulation Process An exemplary representation of an embodiment of a dye encapsulation process 10 is shown in Figure 1. In general terms, the exemplary method shown in Figure 1 involves dissolving a dye 12 and an amphiphilic block copolymer 14 in an organic solvent 16, such as THF, to form a mixture, and then adding the mixture 18 to water 20 under conditions suitable for encapsulation to form composite particles 22. As shown in Figure 1, the amphiphilic block copolymer 14 encapsulates the dye 12 and comprises a hydrophobic core 24 and a hydrophilic shell 26. Three different basic procedures for making micelles were used:
[0146] Basic Encapsulation Step 1 In one embodiment, about 50 mg of dye and 50 mg of block copolymer were dissolved in 10 mL of THF. Optionally, gentle heat can be applied to aid in dissolving the block copolymer. 90 mL of MilliQ™ water was rapidly stirred at 1200 rpm in a beaker. Using a Pasteur pipette, the dye and block copolymer solution was added to the stirring water at room temperature over a period of 3.5 minutes.
[0147] Basic Encapsulation Procedure 2 Approximately 100 mg of dye and 100 mg of block copolymer were dissolved in 20 mL of THF. Optionally, gentle heat can be applied to aid in dissolving the copolymer in THF. 10 mL of the resulting dye / copolymer solution was taken up using a syringe and placed in a syringe pump. The dye / copolymer solution in the syringe was added to 90 mL of ultrapure water at a rate of 2.115 mL / min while stirring at 1200 rpm.
[0148] Optionally, the resulting aqueous micellar solution containing the composite particle composition was centrifuged at 14,000 rpm for 30 minutes and the supernatant containing the composite particle composition was retained.
[0149] Basic Encapsulation Step 3 Approximately 100 mg of dye and 100 mg of block copolymer were dissolved in 20 mL of THF. Optionally, gentle heat can be applied to aid in dissolving the copolymer in THF. 10 mL of the resulting dye / copolymer solution was taken up in a syringe fitted with a needle. Another syringe fitted with a needle took up 10 mL of ultrapure water. The syringe containing the dye / copolymer solution and the syringe containing the ultrapure water were connected to each arm of a confined impinging jet (CIJ) mixer. The contents were mixed in the CIJ to perform flash nanoprecipitation (FNP). The resulting mixture was added dropwise to 80 mL of ultrapure water while stirring at 1200 rpm.
[0150] Optionally, the resulting aqueous micellar solution containing the composite particles was centrifuged at 14,000 rpm for 30 minutes and the supernatant containing the composite particle composition was retained.
[0151] Example 3 Composite particles of Exciton ABS594, 456 and Epolight5843 Epolight 5843 The dye Epolight™ 5843 was encapsulated using the basic encapsulation procedure 1 with the diblock copolymer PEG5000-PS1600. Figure 2 shows a comparison of the UV-Vis spectra of the dye before and after encapsulation. The UV-Vis spectrum obtained in THF shows that the non-encapsulated dye Epolight 5843 has a maximum absorbance peak at 445 nm with a FWHM of 51 nm. Upon encapsulation, a small spectral shift of the dye was observed, with the resulting wavelength of maximum absorbance at 451 nm with a FWHM equal to 80 nm. The peak broadening and shift shown in Figure 2 indicate the formation of a composite particle. Without wishing to be bound by theory, it is possible that changes in the immediate environment of the dye molecules upon encapsulation (e.g., different solvent interactions, different packing of the dye molecules within the composite particle) could lead to changes in the absorbance spectrum. However, since the peak shift is small and the broadening is minimal, the composite particle composition would retain its ability to selectively block a certain narrow range of wavelengths as an optical filter.
[0152] Figure 3 shows the physical appearance of the dye in water and THF, and the physical appearance of the encapsulated dye in an aqueous environment. The dye is hydrophobic and insoluble in water. In a high water content environment, the non-encapsulated dye did not dissolve and precipitated as pellets in the bottle. The encapsulated dye composite particle composition was uniformly dispersed in the aqueous medium.
[0153] Exciton® ABS 594 and 456 The dyes Exciton ABS594 and 456 were individually formulated into composite particles following the reference encapsulation procedure 1 using block copolymers PEG5000-PS1600. A comparison between the UV-Vis spectra of the dyes with and without encapsulation is shown in Figures 4 and 5. Figure 4A shows a comparison of the dye Exciton ABS594, while Figure 5A shows a comparison spectrum of the dye Exciton ABS456. Similar results were observed in comparison with Epolight 5843.
[0154] 4B and 5B show the calibration curves of the encapsulated dyes Exciton ABS594 and 456 in 10% THF and 90% water, respectively, showing the extinction coefficients of each of the composite particle compositions. A series of dilutions of the composite particles in 10% THF were generated and absorbance spectra were collected. The absorbance at the wavelength of maximum absorbance of each dye was used to generate a calibration curve for each encapsulated dye solution. The dye concentration values were calculated assuming 100% encapsulation efficiency. The resulting extension coefficients show that the dye Exciton ABS456 has a lower absorbance than Exciton ABS594.
[0155] Example 4 Particle size and polydispersity of composite particles The composite particle compositions of ABS594 and ABS456 prepared according to the basic encapsulation procedure 1 using block copolymer PEG5000-PS1600 were further characterized by electron tunneling microscopy (TEM) and dynamic light scattering (DLS). Representative TEM images of ABS594 and ABS456 encapsulated particles are shown in Figures 6A and 7A, respectively. The resulting particle size characterization by DLS is shown in Figures 6B and 7B.
[0156] TEM results indicate polydisperse particle sizes ranging from 50 to 170 nm in diameter. ABS594 particles qualitatively appeared more aggregated than ABS456. DLS characterization revealed particle sizes ranging from approximately 120 to 350 nm.
[0157] Example 5 Notch Filtering A mixture of Exciton ABS594 and 456 composite particles was prepared according to the basic encapsulation procedure 1 using block copolymer PEG5000-PS1600, and the UV-Vis absorbance spectrum was obtained and shown in Figure 8. For example, the ratio of the two dyes can be modified and controlled according to the calibration curves as shown in Figures 4 and 5. The absorbance spectrum of the mixed encapsulated dyes demonstrated that the spectral properties of the individual encapsulated dyes are maintained when mixed. The characteristic peaks at 432 nm and 596 nm are attributed to ABS456 and ABS594, respectively. The mixing process did not result in any significant further peak broadening.
[0158] Example 6 Comparison between basic encapsulation procedures 1-3 To compare the efficiency of the three procedures, 100 mg of Exciton ABS456 dye was formulated into composite particles with 100 mg of block copolymer PS(1500)-PEO(6200) using basic encapsulation procedures 1-3. For each method, 0.5 mL of the composite particle composition solution was pipetted using a volumetric pipette and added to 50 mL of ultrapure water. The blank used was ultrapure water. UV-Vis absorbance was measured using a UV-Vis spectrometer (Agilent Cary60 spectrophotometer).
[0159] Figure 9A shows the UV-Vis absorbance of free Exciton ABS456 dye in THF and encapsulated dye composite particles in aqueous solution prepared using basic encapsulation procedure 2 with a syringe pump. Figure 9B shows an overlay of the UV-Vis absorbance spectra of centrifuged encapsulated dye composite particles in aqueous solution prepared using a syringe pump (basic encapsulation procedure 2) or using a Pasteur pipette (basic encapsulation procedure 1). Figure 9C shows an overlay of the UV-Vis absorbance spectra of centrifuged encapsulated dye composite particles in aqueous solution prepared using a syringe pump (basic encapsulation procedure 2) or by FNP (basic encapsulation procedure 3).
[0160] The same concentration of micelles was used to measure UV-Vis absorbance, and the absorbance of the micelles made using a syringe pump was higher than that made using a Pasteur pipette, so in certain embodiments, encapsulation using a syringe pump may be more effective than a Pasteur pipette. Furthermore, the results show that in certain embodiments, encapsulation of dyes using FNP may be more effective than using a syringe pump. Nevertheless, all three methods can be used to prepare the composite particle compositions of the present application.
[0161] Example 7 Stability of Composite Particle Compositions Stability over time Composite particle compositions prepared with dye Exciton ABS456 and block copolymer PS(1500)-PEO(6200) using basic encapsulation procedure 3 were stored in aqueous solution at room temperature (rt) in the dark for up to 11 weeks. Aliquots were taken after 1 day, 1 week, 3 weeks, 7 weeks, and 11 weeks. UV-Vis absorbance spectra were collected to evaluate the stability of the composite particle compositions. Figure 10 shows an overlay of the UV-Vis spectra of aliquots taken at various time points. The results show that the light absorption of the composite particle compositions remains substantially unchanged over time.
[0162] Stability against UV fading Exciton ABS456 A solution of free dye Exciton ABS456 in 90% THF and 10% water was placed in a quartz cuvette. 1 mL of a composite particle composition prepared with dye Exciton ABS456 and block copolymer PS(1500)-PEO(6200) using Basic Encapsulation Procedure 3 above was diluted with 50 mL of 10% THF / 90% water. The diluted composite particle solution was placed in another quartz cuvette. The cuvette containing the free dye solution and the cuvette containing the composite particle solution were charged with 12.8 mW / cm 2The samples were exposed to UV light at 37 °C for 30 min. UV-Vis spectra were acquired before and after 10, 20, and 30 min of UV exposure.
[0163] Figure 11A shows a comparison of the UV-Vis absorbance spectra of the free dye before and after UV exposure for various times. The decrease in light absorbance at the 458 nm absorption peak indicates that the free dye Exciton ABS456 has faded under UV.
[0164] Figure 11B shows a comparison of the UV-Vis absorbance spectrum of the composite particles before and after UV exposure for various times. The absorbance spectrum is substantially unchanged, suggesting that the composite particle composition is stable under UV.
[0165] DLS experiments were performed on the composite particle composition before and after UV exposure to evaluate particle size and polydispersity characteristics. Figure 12 Panels A and B show the number and intensity distributions of the composite particle composition before UV exposure, respectively. Figure 12 Panels C and D show the number and intensity distributions of the composite particle composition after UV exposure, respectively. Figure 12 Panels E and F show scanning electron microscope images of the composite particle composition before and after UV exposure, respectively, confirming the presence of composite particles after UV exposure.
[0166] Exciton ABS594 The same UV stability test as above was repeated for the free dye Exciton ABS594 and composite particles of Exciton ABS594 and block copolymer PS(1500)-PEO(6200) prepared according to basic encapsulation procedure 3. Similar results were observed. The free dye solution in 90% THF / 10% water had a UV intensity of 12.8 mW / cm 2 After 30 min of UV exposure at 100° C., the color faded, while the composite particles remained substantially unchanged.
[0167] The results of the UV stability test showed that the structure of the composite particles was more stable to UV exposure than the free dye.
[0168] Example 8 thermal stability 1 mL of composite particles prepared with dye Exciton ABS456 and block copolymer PS(1500)-PEO(6200) using basic encapsulation procedure 3 above was diluted with 50 mL of 10% THF / 90% water. The maximum absorbance in the UV-Vis spectrum was determined to be less than 1. Ultrapure water was used as a blank for the spectroscopic measurements.
[0169] The UV-Vis absorbance of the diluted solution was taken before heating. Approximately 8 mL of the diluted solution was placed in a round bottom flask. The round bottom flask was placed in a reaction block, fitted with a condenser and running cold water. The contents of the round bottom flask were heated for 15 minutes after which the temperature reached 100°C. After 15 minutes, the heating was stopped and the round bottom flask was allowed to cool to room temperature. The UV-Vis absorbance of the heated solution was taken again.
[0170] Figure 13 shows a comparison of the UV-Vis absorbance spectra of composite particles of the dye Exciton ABS456 before and after heating. Although the maximum UV-Vis absorbance is slightly reduced, the peak wavelength of absorbance is not affected.
[0171] A similar thermal stability test was performed using the dye Exciton ABS594 (free dye, formulated as composite particles with block copolymer PS(1500)-PEO(6200) using basic encapsulation procedure 3 above) using the procedure described above. The diluted composite particle composition was heated to 90° C. for 2 hours in 10% THF / 90% water. Figure 14 shows that the absorbance spectrum of the composite particle is substantially unchanged before and after heating.
[0172] The thermal stability results show that the composite particles are stable enough to be heated to high temperatures for various lengths of time in water and THF, making them suitable for manufacturing processes.
[0173] Example 9 Stability in organic solvents Composite particles were prepared with the dye Exciton ABS456 and block copolymer PS(1500)-PEO(6200) using the basic encapsulation procedure 3 described above. 1 mL of the composite particle solution was diluted with 50 mL of 90% THF / 10% water. The maximum absorbance of the UV-Vis spectrum was determined to be less than 1.
[0174] 1 mL of the diluted composite particle solution was added to a quartz cuvette. 2.5 mL of a 50% THF / 50% water mixture was added to the cuvette. UV-Vis absorbance spectra were obtained immediately after the addition of the THF / water mixture and after 30 minutes of incubation at room temperature after the addition.
[0175] After 30 min of room temperature incubation, the cuvette was placed in a photochemical chamber reactor and exposed to 12.8 mW / cm 2 The samples were then exposed to UV for 10 min at 37 °C for 10 min. The UV-Vis absorbance spectra were recorded again after UV exposure.
[0176] The above procedure was repeated using 10% THF / 90% water.
[0177] To test the stability of the composite particles in 99% THF / 1% water, 0.5 mL of the composite particles prepared according to the basic encapsulation procedure 3 was added undiluted to 50 mL of THF. UV-Vis absorbance spectra were recorded at t = 0 min (immediately after addition), t = 30 min (after 30 min incubation at room temperature), and 12.8 mW / cm 2 The images were collected after 10 min of UV exposure at 40°C.
[0178] Figure 15A shows the UV-Vis absorbance spectra of composite particles of Exciton ABS456 at 35% v / v final THF concentration at different time points in the experiment. The absorbance spectrum was essentially unchanged after 30 min of incubation and after UV bleaching.
[0179] Figure 15B shows the UV-Vis absorbance spectra of composite particles of Exciton ABS456 at 10% v / v final THF concentration at different time points in the experiment. The absorbance spectrum was essentially unchanged after 30 min of incubation and after UV bleaching.
[0180] Figure 15C shows the UV-Vis absorbance spectra of composite particles of Exciton ABS456 at 64% v / v final THF concentration at different time points in the experiment. The absorbance spectrum was essentially unchanged after 30 min of incubation and after UV bleaching.
[0181] Figure 15D shows the UV-Vis absorbance spectra of composite particles of Exciton ABS456 at 99% v / v final THF concentration at different time points in the experiment. The absorbance spectrum was essentially unchanged after 30 min of incubation and after UV bleaching.
[0182] The results show that the composite particles are stable in various concentrations of the organic solvent THF and are stable to UV fading in organic solvents. In contrast, see FIG. 11A, the free dye Exciton ABS456 is not stable to UV fading in 90% THF / 10% water.
[0183] Example 10 Inclusion in hydrogel Si-PDMS macromers were prepared and reacted with polyethylene glycol methyl acrylate. The UV activator diethoxyacetophenone was added to the mixture. Polymerization was induced by UV light. Encapsulated ABS456 or ABS594 nanoparticles were added to the mixture just before UV polymerization.
[0184] A polyacrylamide gel was prepared using a stock solution containing 1.50 mL of water, 2.15 mL of 40% acrylamide, 1.25 mL of TRIS buffer (pH=8.6), 50 μL of tetramethylethylenediamine (TEMED), 50 μL of 10% ammonium persulfate, and approximately 200 μL of the encapsulated dyes ABS456 and ABS594. The gel was cast between two glass plates with a gel thickness of 1 mm.
[0185] Figure 16 shows the optical images and Figure 17 shows the absorbance spectra of polyacrylamide gels doped with ABS594 and ABS456 encapsulated dye micelles. The spectral properties of the encapsulated dyes were maintained after doping into polyacrylamide gels.
[0186] Example 11 Method for preparing composite particles Zn(II) 5,10,15,20-(tetraphenyl)porphyrin and block copolymer poly(1,2-butadiene) 31500 -b-Poly(methyl methacrylate) 21000 Different methods of forming composite particles were tested using a 3D printer. These methods included flash nanoprecipitation (FNP), direct injection, sonication, and vortexing. The confined impinging jet (CIJ) mixers used were manufactured by 3D printing and made of high temperature resin. Each method had five replicates for testing for reproducibility. Samples were analyzed using DLS and a spectrophotometer to measure particle size, polydispersity, photobleaching rate, and absorbance reproducibility.
[0187] Methodology description All samples were derived from the same stock of 2,500 mg / mL block copolymer and dye. Using different methods of nanoparticle formation, 1 ml of stock was mixed with 9 ml of deionized water. In the vortex method, 1 ml of stock was slowly added to the inner wall of a centrifuge tube containing 9 ml of deionized water and vortexed for 60 seconds. In the FNP method, 8 ml of water was stirred, then 1 ml of water and 1 ml of stock solution were injected to form nanoparticles. In the direct injection method, 9 ml of water was stirred in a vial, then 1 ml of stock solution was injected through a needle. The sonicator had 9 ml of water, and 1 ml of stock solution was added while the sonicator was on. All samples were centrifuged after formation. All samples were analyzed by spectrophotometer (Agilent 8453) and DLS (Brook-Haven BI-200SM) to measure particle size, polydispersity, photobleaching rate, and absorbance reproducibility. The samples measured on the spectrophotometer were diluted to 2.5 mg / mL of dye and polymer using deionized water.
[0188] result Reproducibility of the formation methods assessed using UV / Vis spectroscopy. Figure 18 shows the UV-Vis absorbance spectra of the composite particles made by each method. The average peak absorbance of the composite particles made by each method is shown in Table 1. Although the direct injection and FNP methods showed the highest absorbance, each method was successful in encapsulating the dye.
[0189] [Table 1]
[0190] The reproducibility of the formulation methods was evaluated using particle size analysis. The average particle size for each method is shown in Table 2. All samples show similar particle size diameters with standard deviations ranging from 11.6 to 7.6 nm. The FNP method and sonication show errors of 14% and 13%. Direct injection and vortex show errors of 20% and 22%.
[0191] [Table 2]
[0192] The study shows that all four methods were able to form nanoparticles.
[0193] Example 12 Encapsulation Efficiency The efficiency of encapsulating the dye into the composite particles was tested by flocculation. A flocculating agent (e.g., calcium chloride (CaCl2)) was used to separate the free dye from the encapsulated dye. The flocculating agent can selectively aggregate the nanoparticles containing the dye without agglomerating the free dye. CaCl2 concentration and its effect on absorbance
[0194] Zn(II)TPP and poly(1,2-butadiene) 31500 -b-Poly(methyl methacrylate) 21000 Three test samples were prepared using: 1. 2500 mg / mL free dye in tetrahydrofuran (THF); 2. 2500 mg / mL of the copolymer in tetrahydrofuran (THF); and 3. 2500 mg / mL copolymer and 2500 mg / mL free dye in tetrahydrofuran (THF).
[0195] Each stock solution is then used to prepare samples using the direct injection method, in which 1 mL of sample in THF is injected into 9 mL of aqueous solution while stirring in a beaker. The needle tip is submerged and pointed in the direction of stirring. The sample is left stirring for 5 minutes.
[0196] In this experiment, four things need to be tested: the absorbance of the dye with and without CaCl2, determine the concentration of CaCl2 at which the difference in dye content is negligible, verify that this concentration of CaCl2 precipitates from all polymer micelles, and run this CaCl2 concentration repeatedly on the polymer with encapsulated dye to verify the efficiency of encapsulation.
[0197] Four tests were performed on the dye samples: 1. Stir the dye for 1 hour and then centrifuge. 2. Dye + 25mg / mL CaCl2 is stirred for 1 hour and then centrifuged. 3. Stir dye + 50mg / mL CaCl2 for 1 hour and then centrifuge. 4. Stir the dye + 100 mg / mL CaCl2 for 1 hour and then centrifuge.
[0198] Each sample was then measured in a UV-Vis spectrophotometer to determine the dye content. In parallel with these tests, samples of the polymer were tested to see if all of the polymer had precipitated. 1. Stir the polymer for 1 hour and then centrifuge it. 2. Polymer + 25 mg / mL CaCl2 was stirred for 1 hour and then centrifuged. 3. Polymer + 50 mg / mL CaCl2 was stirred for 1 hour and then centrifuged. 4. Polymer + 100 mg / mL CaCl2 is stirred for 1 hour and then centrifuged.
[0199] These samples were evaluated by DLS to determine if particles were still present.
[0200] The absorbance of the dye in the presence and absence of CaCl2 was determined by measuring the absorbance of solutions containing various amounts of CaCl2. This method also determines the amount of CaCl2 that does not affect the aggregation of the dye. It was found that when CaCl2 was below 100 mg / mL, there was a negligible difference in the amount of dye present compared to samples without CaCl2.
[0201] DLS measurements performed on polymers with added CaCl2 show that no nanoparticles were detected when 100 mg / mL and 50 mg / mL CaCl2 were added. When 25 mg / mL CaCl2 was added, some small particles were observed, but were very difficult to measure. Finally, when no CaCl2 was added, nanoparticles were observed, with an average particle size of 55 nm and a PDI of 0.117. 50 mg / mL can be used to determine encapsulation efficiency, as it does not affect the dye concentration and removes all the polymer.
[0202] Zn(II)TPP and block copolymer poly(1,2-butadiene) 31500 -b-Poly(methyl methacrylate) 21000 The composite particles are compared to particles formed with only the amphiphilic block copolymer and only the dye to evaluate encapsulation efficiency. The test items were tested in triplicate.
[0203] Zn(II)TPP and poly(1,2-butadiene) 31500 -b-Poly(methyl methacrylate) 21000 Three test samples were prepared using: 1. 250 mg / mL of free dye in tetrahydrofuran (THF) / water in a 1:9 ratio; 2. 250 mg / mL copolymer in tetrahydrofuran (THF) / water in a 1:9 ratio; 3. 250 mg / mL copolymer and 250 mg / mL free dye in tetrahydrofuran (THF) / water in a 1:9 ratio.
[0204] Prepare each sample using the direct injection method, in which 1 mL of sample in THF is injected into 9 mL of aqueous solution in a beaker while stirring. The needle tip is submerged and pointed in the direction of stirring. Leave the sample stirring for 5 minutes.
[0205] 3 mL of each sample was then added to a separate vial. A solution of CaCl2 was made so that the final concentration added to each sample was 100 mg / mL. Each sample was stirred for 1 hour, this time resulting in the precipitation of all the polymer solution, not the dye solution, and the dye-encapsulated micellar solution resulting in the precipitation of the colored sample, with some dye remaining in solution as in Attempt 3. Each sample was then centrifuged at 4000 RPM using an 80-02 electronic centrifuge for 1 hour and then decanted. This removed the solid particles but kept the free dye in solution. The samples were measured on a UV-Vis spectrophotometer and absorbance and dynamic light scattering (DLS) were measured using a Brookhaven BI-200SM dynamic light scattering instrument.
[0206] The solution containing only the polymer showed no absorbance of the dye (as expected, no dye was added to the solution at all). (Figure 19) The solution containing the dye showed a very large peak for the zinc(II) 5,10,15,20-(tetraphenyl)porphyrin dye, was highly diluted and broad. The broadness could be explained due to the solution conditions (water) and dilution factor, as none of the dye should have been removed. Finally, the solution containing the dye and polymer showed some absorbance (about 1 / 10 the absorbance of the dye solution). This indicates that a significant portion of the dye was removed compared to the free dye. The dye removed should have been the encapsulated dye, leaving residual free dye.
[0207] conclusion The amount of free dye in the solution was determined after flocculating all of the encapsulated dye from the solution. The flocculant used was calcium chloride (CaCl2), which can ionically bind to the nanoparticle solution and pull it out of solution. The flocculant can selectively flocculate the nanoparticles containing the dye without flocculating the free dye. High concentrations of calcium chloride, 33300 mg / mL and 1660 mg / mL, flocculate the solution of the dye encapsulated in the nanoparticles as well as flocculate the aggregated free dye. Low concentrations of 100 mg / mL and 50 mg / mL flocculate the dye encapsulated in the nanoparticles but not the free dye. The absence of nanoparticles in the solution after the addition of calcium chloride was also found by DLS. After adding 50 mg / mL of calcium chloride to the solution of the dye encapsulated in the nanoparticles and 50 mg / mL of calcium chloride to the free dye, absorbance measurements were taken to determine the amount of dye not encapsulated between the nanoparticles. The ratio of the absorbance measurements indicates the percentage of encapsulation, where the average corrected absorbance of the free dye solution is 55.8 and the average corrected absorbance of the encapsulated dye solution is 1.33. Comparing these values gives an encapsulation efficiency of 97.6%.
[0208] Using calcium chloride as the flocculant, selective flocculation can occur in samples of dyes encapsulated in micelles. Poly(1,2-butadiene) 31500 -b-Poly(methyl methacrylate) 21000 Micelles formed using zinc(II) 5,10,15,20-(tetraphenyl)porphyrin (dye) in the (diblock-co-polymer) are tested and show an encapsulation efficiency of 97.6%% + / - 1.57%.
[0209] Example 13 Encapsulation of different pigments Eleven structurally different hydrophobic dyes were selected to test their ability to be encapsulated by the amphiphilic block copolymers: 1. 1,3,5,7-Tetramethyl-8-(4-hydroxyphenyl)BODIPY (purchased from PorphyChem) (narrow band, visible absorber) 2. 1,7-(di-4,N,N-dimethylaminophenyl)-3,5-(di-4-bromophenyl) AZABODIPY (purchased from PorphyChem) (broadband, visible absorber) 3. 2,3,7,8,12,13,17,18-(octabromo)-5,10,15,20-(tetraphenyl)porphyrin (purchased from PorphyChem) (narrow band, visible absorber) 4. Zinc(II) 2,9,16,23-(tetranitro)phthalocyanine (purchased from PorphyChem) (broadband, UV absorber) 5. 2,3,6,7-Tetrahydro-9-(trifluoromethyl)-1H,5H,11H-[1]benzopyrano(6,7,8-ij)quinolizin-11-one (99% dye content), also known as Coumarin 153 (purchased from Sigma Aldrich) (broadband, visible absorber) 6. 2,5,7,8-Tetramethyl-2-(4,8,12-trimethyltridecyl)-3,4-dihydro-2H-1-benzopyran-6-yl acetate (>95.5%, liquid), also known as vitamin E or α-tocopherol (purchased from Sigma Aldrich) (broadband, UV absorber) 7. 1,3,3-trimethyl-2-[(1E,3E,5E,7E,9E,11E,13E,15E,17E)-3,7,12,16-tetramethyl-18-(2,6,6-trimethylcyclohexen-1-yl)octadeca-1,3,5,7,9,11,13,15,17-nonayenyl]cyclohexene (>93%, powder), also known as β-carotene (broadband, visible absorber) 8. Perylene (>99%) (purchased from Sigma Aldrich) 9. Vanadyl 2,3-naphthalocyanine (purchased from Sigma Aldrich) (narrow band, visible and near infrared absorber) 10. P-Quarterphenyl (>98%) (purchased from TCI AMERICA) (broadband, UV absorber) 11. 2-[3-(2H-benzotriazol-2-yl)-4-hydroxy-phenyl]ethyl methacrylate (99%), also known as NORBLOC™ (purchased from Sigma Aldrich)
[0210] For encapsulation, t-butyl methacrylate (8300)-b-polyethylene oxide (5900) (purchased from Polymer Source Inc.) was used.
[0211] 1:9 tetrahydrofuran in deionized water (10% v / v THF in DI water) was used as the solvent.
[0212] Keep all chemicals and solvents at room temperature and keep Vitamin E in a dark environment to avoid UV degradation.
[0213] The following 11 types of composite particles were prepared: 1. 1,3,5,7-Tetramethyl-8-(4-hydroxyphenyl) BODIPY in poly(t-butyl methacrylate) (8300)-b-poly(ethylene oxide) (5900) 2. 1,7-(di-4,N,N-dimethylaminophenyl)-3,5-(di-4-bromophenyl) AZABODIPY in poly(t-butyl methacrylate)(8300)-b-poly(ethylene oxide)(5900) 3. 2,3,7,8,12,13,17,18-(octabromo)-5,10,15,20-(tetraphenyl)porphyrin in poly(t-butyl methacrylate) (8300)-b-poly(ethylene oxide) (5900) 4. Zinc(II) 2,9,16,23-(tetranitro)phthalocyanine in poly(t-butyl methacrylate)(8300)-b-poly(ethylene oxide)(5900) 5. Coumarin 153 in poly(t-butyl methacrylate) (8300)-b-poly(ethylene oxide) (5900) 6. Vitamin E in poly(t-butyl methacrylate) (8300)-b-poly(ethylene oxide) (5900) 7. β-Carotene in poly(t-butyl methacrylate) (8300)-b-poly(ethylene oxide) (5900) 8. Perylene in poly(t-butyl methacrylate) (8300)-b-poly(ethylene oxide) (5900) 9. p-Quarterphenyl in poly(t-butyl methacrylate) (8300)-b-poly(ethylene oxide) (5900) 10. Vanadyl 2,3-naphthalocyanine in poly(t-butyl methacrylate) (8300)-b-poly(ethylene oxide) (5900) 11. 2-[3-(2H-benzotriazol-2-yl)-4-hydroxy-phenyl]ethyl methacrylate in poly(t-butyl methacrylate) (8300)-b-poly(ethylene oxide) (5900)
[0214] Encapsulation Encapsulation was carried out following a standard flash nanoprecipitation procedure in a 9:1 deionized water-THF solvent system. 2 ml of 2500 mg / mL poly t-butyl methacrylate (8300)-b-polyethylene oxide (5900) and dye solution was loaded into a 3 mL syringe and 2 ml of deionized water was prepared in another syringe and then used to carry out the encapsulation procedure.
[0215] Characterization The primary validation method used to verify successful encapsulation is transmission electron microscopy (TEM). To obtain clear images, the 250 mg / mL post-FNP solution was diluted 100-fold to 2.5 mg / mL using the same solvent system and then filtered using a 450 nm filter. The filtered samples were dried for 24 hours and measured using a FEI Tecnai™ 120 kV transmission electron microscope. Images were captured in the most representative areas where the particles had well-defined edges, dense cores, and consistent shapes.
[0216] Dynamic light scattering (DLS) was used as a secondary method to detect the presence of nanoparticles. To obtain accurate measurements, the 250 mg / mL post-FNP solution was diluted 100-fold to 2.5 mg / mL using filtered deionized water and then filtered using a 450 nm filter to remove airborne particles. The filtered samples were measured using a Brook-Haven BI200-SM dynamic light scattering method. Each sample was measured in triplicate and the particle size was then interpreted as NNLS, CONTIN, or effective diameter.
[0217] The post-FNP spectra were measured using an Agilent 8653 spectrophotometer capable of measuring the infrared region. To obtain the most accurate spectral data, the samples were diluted to an absorbance range of 0.5–1 using the same solvent system.
[0218] result Using the same poly(t-butyl methacrylate) (8300)-b-polyethylene oxide (5900) diblock copolymer and a 9:1 deionized water-THF solvent system, eleven dyes were successfully encapsulated. These dyes included: 1. 1,3,5,7-Tetramethyl-8-(4-hydroxyphenyl)BODIPY 2. 1,7-(di-4,N,N-dimethylaminophenyl)-3,5-(di-4-bromophenyl) AZABODIPY 3. 2,3,7,8,12,13,17,18-(octabromo)-5,10,15,20-(tetraphenyl)porphyrin 4. Zinc(II) 2,9,16,23-(tetranitro)phthalocyanine 5. Coumarin 153 6. Vitamin E 7. Beta-Carotene 8. Perylene 9. P-Quarterphenyl 10. Vanadyl 2,3-naphthalocyanine 11. 2-[3-(2H-benzotriazol-2-yl)-4-hydroxy-phenyl]ethyl methacrylate Includes:
[0219] 20-21(A-K) show TEM images and UV-Vis absorption data of particles encapsulating different dyes, demonstrating that different dyes can be encapsulated in amphiphilic block copolymers while retaining their UV-Vis absorption properties. The particle size and polydispersity results measured by DLS along with UV-Vis absorbance are summarized in Table 3.
[0220] [Table 3A]
[0221] [Table 3B]
[0222] Example 14 Crosslinking in amphiphilic block copolymers Glutaraldehyde crosslinking 20 mL of stock composite particles were made using standard methods (described in Example 11 above) in which the diblock copolymer and hydrophobic dye were dissolved in 2 mL of THF at a concentration of 2500 mg / mL for both, then injected into a hot resin-confined impinging jet (CIJ) mixer with another 2 mL of deionized (DI) water, and these solutions were added dropwise to 16 mL of DI water. Since it was observed that higher concentrations of particles resulted in inter-micellar cross-linking and visible aggregation and precipitation of suspended micelles, zinc(II) tetraphenylporphyrin-loaded PVA(2,500)-PMMA(25,000) was diluted 1000 times compared to the stock and used for cross-linking experiments. The concentrations of the reagents can be adjusted to avoid aggregation due to inter-micellar cross-linking.
[0223] Glutaraldehyde (GA) was added to each of these solutions at various concentrations, corresponding to molar ratios of 8.9%, 13.4%, and 26.8% relative to the PVA end of the diblock copolymer. Once GA was added to each sample, the samples were allowed to react for 24 hours at room temperature prior to DLS measurements. A fourth particle sample was prepared at the same dilution rate, but without the addition of GA, to serve as a control for particle size.
[0224] The results of particle size analysis using DLS are shown in Table 4.
[0225] [Table 4]
[0226] Polybutadiene Crosslinking A stock THF solution was made with 50 mg / mL of polymer. The samples were then treated with a crosslinker at a concentration of 1% by weight relative to the polybutadiene, and optionally with 1% by weight of TRIS. The test articles were made using a high-temperature resin-confined impinging jet (CIJ) mixer. After making, the particles were inserted into a Falcon tube and centrifuged at 4000 rpm for 30 minutes using a Canfort 80-2 Electronic Centrifuge. The samples were then heated at 80° C. for 24 hours.
[0227] The samples with polybutadiene crosslinks show increased solvent resistance, suggesting that internal core crosslinking has occurred. CS18 (no crosslinking) does not survive ethanol exposure, whereas CS38 (polybutadiene crosslinking) does survive ethanol exposure.
[0228] Tetraethyl orthosilicate (TEOS) crosslinking 20 mL of particle solutions were created containing 100 mg of polymer, 100 mg of zinc(II) tetraphenylporphyrin (Zn(II)TPP), and 1 mL (0.933 g) of TEOS. These were formed using the direct injection method by dissolving the materials in 2 mL of THF and injecting into 17 mL of water (TEOS was added in 1 mL, for a total volume of 20 mL). The following systems were tested: ·(1,2)PbD(15,000)-b-PAA(6,500) loaded with Zn(II)TPP and cross-linked using TEOS. ·(1,2)PbD(31,500)-b-PMMA(21,000) filled with Zn(II)TPP and cross-linked using TEOS. ·PS(1,300)-b-PEO(5,600) filled with ZnTPP and cross-linked using TEOS.
[0229] A control sample was prepared in the same manner as the experimental sample above, except that it did not contain any polymer or dye, and was also prepared using the direct injection method by adding 1 mL (1.21 g) of TEOS to 2 mL of THF and injecting into 17 mL of water.
[0230] Each sample was made using its own individual stock solution containing polymer, ZnTPP, and TEOS - the stock solutions were mixed for 48 hours to ensure the materials were dissolved, and then made by direct injection into DI water. These were made at high concentrations due to the amount of material required to successfully perform solid-state nuclear magnetic resonance (ssNMR) measurements. After making, a small aliquot was removed for SEM testing and diluted 100-fold, and these samples were subsequently lyophilized to remove all water and THF for measurement using ssNMR.
[0231] Magic Angle Spinning (MAS) 1 H NMR was performed to determine the delay time of the slowest proton in the sample at 0.2 ppm, which corresponds to the hydrogen nucleus close to the silicon nucleus. 29 We performed Si cross-polarization experiments to measure the environment of these silicon nuclei. Cross-polarization is a method to measure the environment of the highly sensitive nuclei ( 1 H) polarization with low sensitivity nuclei ( 29 In addition, this technique allows the observation of silicon nuclei in close proximity to polymer hydrogen, which is embedded in the silicon shell of the micelles. 29 This effectively enables the measurement of Si nuclei.
[0232] 29 Si and 1 H magic angle spinning (MAS) NMR experiments were performed in the NMR-3 at the Chemistry Department of Dalhousie University with a 9.4 T magnet (400.24 MHz proton Larmor frequency, 79.52 MHz 29 The measurements were performed on a Bruker Avance DSX NMR spectrometer equipped with a Si Larmor frequency of 1.00 kHz. The samples were packed in a 4 mm diameter rotor and spun at 7.00 kHz.
[0233] Particle-related 29 For Si cross polarization (CP) / MAS data, 1 You need to know the H parameters: 1 H MAS NMR spectra were acquired under a sample spinning frequency of 7 kHz with one pulse excitation followed by background suppression. 1 The relaxation times for the H NMR experiments were determined by inversion recovery sequences and were estimated to be on the order of 0.84 seconds for the slowest component (at 0.2 ppm). Spectra were acquired with a delay of 4.2 seconds. The chemical shift scale used the conversion factor of IUPAC Recommendation 2001. 29 Referenced to Si chemical shift standard. 29 Si(CP) / MAS NMR experiments were carried out on a 4 mm diameter rotor spinning at 7.0 kHz. 29 Si CP / MAS NMR spectra were acquired with a repetition time of 4.2 s, a CP contact time of 5 ms, and 1024 scans accumulated. Cross polarization (CP) parameters were optimized with kaolin, which also served as the secondary chemical shift standard at −91.0 ppm and −91.5 ppm relative to TMS.
[0234] 29The Si CP / MAS NMR spectrum is shown in Figures 22A-C. Three peaks are seen with shifts of maximum at -91.6 ppm, -101. ppm, and -111.0 ppm. These are in good agreement with typical Q2, Q3, and Q4 chemical shift values, respectively. A control sample was prepared exactly like the experimental sample in this section, but without the addition of polymer or dye. After 96 hours of reaction time and subsequent freeze-drying, a white powder was obtained. Measurements of this control sample should show the signals that non-encapsulated silica shows in the experimental sample. 29 The Si ssNMR spectrum is shown in Figure 22D. These NMR results indicate that TEOS has been successfully hydrolyzed and condensed around the composite particles. In the case of the (1,2)PbD(15,000)-b-PAA(6,500) and PS(1,300)-b-PEO(5,600) polymer systems, there is a very strong signal compared to the noise, indicating that silica is abundant in the measured solids. Without wishing to be bound by theory, this is likely due to the high encapsulation efficiency of these two polymer systems. The low signal to noise ratio observed for (1,2)PbD(31,500)-PMMA(21,000) is likely due to the low encapsulation efficiency of this system.
[0235] Varying TEOS Concentration. 10 mL of particle solutions were made containing 2.5 mg of polymer, 2.5 mg of Zn(II)TPP, and various amounts of TEOS as described below. The polymers tested were: 1. (1,2)PbD(15,000)-b-PAA(6,500) a. Contains 12.5 mg of TEOS b. Contains 5 mg of TEOS c. Contains 2.5 mg of TEOS 2. (1,2)PbD(31,500)-b-PMMA(21,000) a. Contains 12.5 mg of TEOS b. Contains 5 mg of TEOS c. Contains 2.5 mg of TEOS 3. PS(1,300)-b-PEO(5,600) a. Contains 12.5 mg of TEOS b. Contains 5 mg of TEOS c. Contains 2.5 mg of TEOS 4. PMMA(25,000)-b-PVA(2,300) a. Contains 12.5 mg of TEOS b. Contains 5 mg of TEOS c. Contains 2.5 mg of TEOS
[0236] To ensure the same concentration across different samples, one stock solution was prepared for each polymer system containing polymer and Zn(II)TPP - the stock solutions were mixed for 48 h to ensure dissolution of the materials, and then mixed using a high temperature resin confined impinging jet (CIJ) mixer.
[0237] Aliquots were removed and various amounts of TEOS were added to each sample of the same polymer type, and the volumes were corrected using THF to ensure that all samples contained the same concentrations of polymer and Zn(II)TPP in the same stock volume. Once prepared, samples were diluted 400x for measurement by dynamic light scattering (DLS) and 100x for SEM imaging. The remaining samples were retained for use in stability studies.
[0238] All samples were kept at room temperature for a minimum of 96 hours prior to testing to allow the TEOS to react and crosslink around the particle complexes.
[0239] DLS was performed to measure particle size and polydispersity for all four polymer systems tested, and the data are summarized in Tables 5, 6, 7, and 8 below.
[0240] [Table 5]
[0241] [Table 6]
[0242] [Table 7]
[0243] [Table 8]
[0244] The DLS data shows particle sizes ranging from 2 nm up to over 100 nm.
[0245] To visualize the particles, the samples were also measured using TEM imaging (Figure 23). Some clumping is observed, however this is likely due to the slow drying of the water and the sticky nature of the polymer when dry, as the DLS data does not show significant aggregation.
[0246] In this study, synthetic polymeric micelles were formed using various polymer systems: (1,2)PbD(15,000)-b-PAA(6,500), (1,2)PbD(31,500)-b-PMMA(21,000), PS(1,300)-b-PEO(5,600), and PMMA(25,000)-b-PVA(2,300). These were successfully crosslinked via TEOS hydrolysis and condensation around the particles. The control sample shows that non-encapsulated polymerized TEOS produces no signal by using cross-polarization / magic angle spinning ssNMR measurements. This lack of signal observed in the control sample confirms that the signal observed in the experimental sample is from the crosslinked silica shell around the particles and that the CP / MAS ssNMR experiment is non-reactive to non-encapsulated silica. The signal is clearly observed in the experimental sample for the NMR study. 29Observing a signal in Si-nucleus cross-polarization experiments requires that the silica nuclei are in close proximity to the polymer protons, so observing a signal in these experiments confirms the presence of polymerized silica around the particles. DLS measurements and SEM imaging confirm the presence of the particles. TEOS cross-linking does not require an encapsulation reaction between TEOS and the polymer, so this cross-linking method can be applied to any polymer system as long as the TEOS is incorporated into the core of the particle. This cross-linking method can be performed when the particles are suspended in aqueous solution to hydrolyze and subsequently condense the TEOS. Due to the silica shell cross-linking demonstrated, TEOS cross-linking can be used in stability studies to determine the effect on stability to solvents, high temperatures, and other manufacturing conditions.
[0247] Example 15 particle drying Poly(1,2-butadiene) 31500 -b-Poly(methyl methacrylate) 21000 Zn(II)TPP was encapsulated using the FNP method described above using 1000 mL of 100% ethanol. Polyethylene glycol 4000 (PEG 4000) was used as a cryoprotectant. Stock solutions of both block copolymer and dye were made in THF at 250 mg / mL. For the FNP method, nanoparticles were formed by stirring 8 ml of water, then 1 ml of water and 1 ml of stock solution. All samples were analyzed by spectrophotometer (Agilent) and DLS (Brook-Haven BI-200SM) to measure particle size, polydispersity, and absorbance. Samples measured by spectrophotometer were diluted to 5 mg / mL of dye and polymer using deionized water. Samples were set to 25 °C while running DLS and room temperature for the spectrophotometer.
[0248] Figure 24 shows the UV-Vis spectrum of freeze-dried composite particles containing a cryoprotectant after resuspension in 90% v / v water / 10% v / v THF. The resuspended particles exhibit a UV absorbance maximum at the same wavelength as the non-lyophilized particles, indicating that the particles are stable to freeze-drying.
[0249] Table 9 shows the particle size analysis of the particle samples before and after freeze-drying with cryoprotectant. The particle size is essentially unchanged.
[0250] [Table 9]
[0251] DLS and TEM data indicate that the stock solution containing PEG4000 is likely the same size after freeze-drying. The stock particle solution containing PEG4000 has an average particle size of 65 nm (standard deviation of 11 nm) and a polydispersity of 0.203 (standard deviation of 0.033). PEG4000 increased the size of the nanoparticles by 20 nm. The nanoparticles were freeze-dried for 24 hours and then resuspended in 10% THF / 90% water. The samples were then diluted with water and measured by DLS. The resuspended samples had a diameter of 62 nm (standard deviation of 11.3 nm) and a polydispersity of 0.205 (standard deviation of 0.023), indicating that the particle size of the resuspended samples was not altered by freeze-drying with cryoprotectant.
[0252] (Example 16) Stability in hydrogel monomers and hydrogel polymers To simulate the consolidation process in contact lens manufacturing, the composite particles of the present disclosure were incorporated into a representative contact lens monomer using M2Dx formulation. The stability of the particles was evaluated by visual inspection and UV / Vis spectroscopy. Fourteen particles and two comparative embodiments of the present disclosure were incorporated, and all were found to withstand exposure to M2Dx monomer. Non-encapsulated zinc(II) 5,10,15,20-(tetraphenyl)porphyrin could also be consolidated. All test articles were uniformly resuspended in M2Dx monomer, and no obvious yellowing or clouding of the solution was observed. Consolidation did not appear to change the optical filtering properties of any of the particle composite embodiments tested. All test articles were then uniformly consolidated into M2Dx polymer by UV curing, and no obvious yellowing or clouding of the contact lens prototype was observed. Consolidation did not appear to change the optical filtering properties of any of the particle composite embodiments tested. Thus, all test articles and control articles passed this contact lens prepolymer study.
[0253] For composite particles to be used in contact lenses, the composite particles are ideally matched to the chemical environment of the contact lens matrix and are suitable for the homogenization and curing conditions of contact lens manufacture.
[0254] In this study, candidate particles were evaluated in representative silicone hydrogel monomer using M2Dx compositions provided by Tangible Science LLC. Nine shell crosslinks, two core crosslinks, two dual crosslinks (both shell and core), and two compositions using both crosslinking methods were evaluated in M2Dx monomer along with three comparative embodiments and two control articles. To simulate the manufacturing process, all test articles were dried by vacuum filtration in the presence of cryoprotectant poly(ethylene glycol) 4000, and then the dried particles were added to M2Dx and homogenized. Primary evaluation was performed by visual inspection and spectral analysis.
[0255] Test items Three comparative particles were made: BC01, PH01 and PN01: ·BC01: Dye-encapsulated nanoparticles {Zinc(II) 5,10,15,20-(tetraphenyl)porphyrin (dye) poly(2-methyloxazoline)2400-b-poly(dimethylsiloxane)5000-b-poly(2-methyl)oxazoline)2400 (triblock copolymer)} ·PH01: Dye-encapsulated nanoparticles {Zinc(II) 5,10,15,20-(tetraphenyl)porphyrin (dye) poly(n-butyl acrylate) 7500-b-poly(acrylic acid) 5500 (diblock copolymer)} Dye-encapsulated nanoparticles {zinc(II) 5,10,15,20-(tetraphenyl)porphyrin (dye) poly(ethylene oxide) 4000-b-poly(propylene glycol) 3000-b-poly(ethylene oxide) 4000 (triblock copolymer)}
[0256] Test articles BC01 and PH01 were synthesized following standard flash nanoprecipitation (FNP) procedures (as described above) in a 9:1 deionized water-tetrahydrofuran solvent system. 6 mL of 2500 mg / L dye block copolymer and 6 mL of deionized water were prepared in two 10 mL syringes. The stock solution was then injected into a 48 mL water bath over the water while stirring. The post-FNP solution was transferred evenly into three scintillation vials.
[0257] Fourteen composite particles of the present disclosure were tested: 1. CS28 (Coloursmith) dye-encapsulated nanoparticles {zinc(II) 5,10,15,20-(tetraphenyl)porphyrin (dye) poly(dimethylsiloxane) 8000-b-poly(acrylic acid) 8000 (diblock copolymer)} shell crosslinked with tetraethyl orthosilicate (5 times the mass of the poly(acrylic acid) block) in the presence of 0.001 M hydrochloric acid at 80 degrees Celsius for 24 hours. 2. Dye-encapsulated nanoparticles {zinc(II) 5,10,15,20-(tetraphenyl)porphyrin (dye) poly(methyl methacrylate) 7400-b-poly(acrylic acid) 24300 (diblock copolymer)} shell crosslinked with tetraethyl orthosilicate (5 times the mass of the poly(acrylic acid) block) in the presence of 0.001 M CS29 (Coloursmith) hydrochloric acid at 80 degrees Celsius for 24 hours. 3. Dye-encapsulated nanoparticles {zinc(II) 5,10,15,20-(tetraphenyl)porphyrin (dye) poly(1,2-butadiene) = -b-poly(acrylic acid) 6500 (diblock copolymer)} shell crosslinked with tetraethyl orthosilicate (5 times the mass of the poly(acrylic acid) block) in the presence of 0.001 M CS30 (Coloursmith) hydrochloric acid at 80 degrees Celsius for 24 hours. 4. CS31 (Coloursmith) dye-encapsulated nanoparticles {zinc(II) 5,10,15,20-(tetraphenyl)porphyrin (dye) poly(dimethylsiloxane) 5000-b-poly(ethylene oxide) 2100 (diblock copolymer)} shell crosslinked with tetraethyl orthosilicate (5 times the mass of poly(ethylene oxide) block) in the presence of 0.001M hydrochloric acid at 80 degrees Celsius for 24 hours. 5. CS33 (Coloursmith) dye-encapsulated nanoparticles {zinc(II) 5,10,15,20-(tetraphenyl)porphyrin (dye) poly(styrene) 1300-b-poly(ethylene oxide) 5600 (diblock copolymer)} shell crosslinked with tetraethyl orthosilicate (5 times the mass of the poly(ethylene oxide) block) in the presence of 0.001M hydrochloric acid at 80 degrees Celsius for 24 hours. 6. CS34 (Coloursmith) dye-encapsulated nanoparticles {zinc(II) 5,10,15,20-(tetraphenyl)porphyrin (dye) poly(n-butyl acrylate) 7500-b-poly(acrylic acid) 5500 (diblock copolymer)} shell crosslinked with tetraethyl orthosilicate (5 times the mass of the poly(acrylic acid) block) in the presence of 0.001 M hydrochloric acid at 80 degrees Celsius for 24 hours. 7. CS35 (Coloursmith) dye-encapsulated nanoparticles {zinc(II) 5,10,15,20-(tetraphenyl)porphyrin (dye) poly(methyl methacrylate) 3000-b-poly(ethylene oxide) 3000 (diblock copolymer)} shell crosslinked with tetraethyl orthosilicate (5 times the mass of the poly(ethylene oxide) block) in the presence of 0.001M hydrochloric acid at 80 degrees Celsius for 24 hours. 8. CS36 (Coloursmith) dye-encapsulated nanoparticles {zinc(II) 5,10,15,20-(tetraphenyl)porphyrin (dye) poly(1,4-butadiene) 9000-b-poly(acrylic acid) 3500 (diblock copolymer)} shell crosslinked with tetraethyl orthosilicate (5 times the mass of the poly(acrylic acid) block) in the presence of 0.001 M hydrochloric acid at 80 degrees Celsius for 24 hours. 9. CS37 (Coloursmith) dye-encapsulated nanoparticles {zinc(II) 5,10,15,20-(tetraphenyl)porphyrin (dye) poly(1,2-butadiene) 15000-b-poly(acrylic acid) 6500 (diblock copolymer)} shell crosslinked with fumed silica (5 times the mass of poly(acrylic acid) block) in the presence of 0.001 M hydrochloric acid at 80 degrees Celsius for 24 hours. 10. CS38 (Coloursmith) Dye-encapsulated nanoparticles {zinc(II) 5,10,15,20-(tetraphenyl)porphyrin (dye) poly(1,2-butadiene) 15000-b-poly(acrylic acid) 6500 (diblock copolymer)} core, initiated with azobisisobutyronitrile (AIBN) and crosslinked by free radical reaction in the presence of trimethylolpropane tris(3-mercaptopropionate) at 80 degrees Celsius for 24 hours. 11. CS39 (Coloursmith) dye-encapsulated nanoparticles {zinc(II) 5,10,15,20-(tetraphenyl)porphyrin (dye) poly(1,4-butadiene) 9000-b-poly(acrylic acid) 3500 (diblock copolymer)} core initiated with azobisisobutyronitrile (AIBN) at 80 °C for 24 hours and crosslinked by free radical reaction in the presence of trimethylolpropane tris(3-mercaptopropionate) 12. Dye-encapsulated nanoparticles {zinc(II) 5,10,15,20-(tetraphenyl)porphyrin (dye)-poly(1,2-butadiene) 15000-b-poly(acrylic acid) 6500 (diblock copolymer)} shell crosslinked using tetraethyl orthosilicate (5 times the mass of poly(acrylic acid) block) in the presence of 0.001M hydrochloric acid CS40 (Coloursmith); core crosslinked by free radical reaction initiated using azobisisobutyronitrile (AIBN) in the presence of trimethylolpropane tris(3-mercaptopropionate) at 80 degrees Celsius for 24 hours. 13. CS41 (Coloursmith) dye-encapsulated nanoparticles {zinc(II) 5,10,15,20-(tetraphenyl)porphyrin (dye) poly(1,4-butadiene) 9000-b-poly(acrylic acid) 3500 (diblock copolymer)} shell crosslinked using tetraethyl orthosilicate (5 times the mass of poly(acrylic acid) block) in the presence of 0.001M hydrochloric acid; core crosslinked by free radical reaction initiated using azobisisobutyronitrile (AIBN) in the presence of trimethylolpropane tris(3-mercaptopropionate) at 80 degrees Celsius for 24 hours. 14. CS42 (Coloursmith) Dye-encapsulated nanoparticles {Zinc(II) 5,10,15,20-(tetraphenyl)porphyrin (dye) poly(methyl methacrylate) 3000-b-poly(ethylene oxide) 3000 (diblock copolymer)}
[0258] Shell crosslinked test items were synthesized by encapsulating tetraethyl orthosilicate (TEOS), five times the mass of the hydrophilic block, into the dye block copolymer stock solution. Hydrochloric acid (HCl) was then added to the water bath at a concentration of 0.001M as an acid catalyst. Particles were produced using FNP and heat treated at 80 degrees Celsius for 24 hours. CS37 was shell crosslinked using fumed silica instead of TEOS. Core crosslinking was achieved by encapsulating the free radical transfer agent trimethylolpropane tris(3-mercaptopropionate (TRIS) and the thermally activated free radical initiator azobisisobutyronitrile (AIBN). The THF used to prepare the stock solution did not contain the free radical inhibitor butylated hydroxytoluene (BHT). After FNP, the particles were heat treated at 80 degrees Celsius for 24 hours.
[0259] Two control items were included: CS00 (Free Pigment) Free Zinc(II) 5,10,15,20-(Tetraphenyl)porphyrin · Empty M2DX prepolymer.
[0260] Dual crosslinked test items (CS40 and CS41) were prepared by combining the two crosslinking methods. AIBN, TRIS, and TEOS were encapsulated at the same concentrations as above along with the dyes using diblock copolymers via FNP. The resulting particle solution was heated at 80 degrees Celsius for 24 hours in the presence of HCl.
[0261] To obtain dry nanoparticles, 10 mg / mL poly(ethylene glycol) 4000 was added to each post-FNP solution as a cryoprotectant, and the particle solutions were then passed through a 30 nm membrane filter and vacuum dried or air dried.
[0262] Preparation of M2Dx prepolymer and particle consolidation 187.5 mL of M2Dx stock solution was prepared by mixing 14 mL methacryloxypropyl-terminated polydimethylsiloxane (M2Dx), 28 mL 3-[tris(trimethylsiloxy)silyl]propyl methacrylate (Tris), 28 mL dimethylacrylamide (DMA) and 17.5 mL 1-hexanol. The solution was stirred and kept in an amber glass bottle to prevent undesired polymerization. The stock was stirred for 24 hours after which the particles were consolidated.
[0263] Because the dry particles could not be separated from the filter, it was not possible to quantitatively transfer the particles from the filter to each prepolymer solution. Therefore, using a scalpel, a 2.0 mm × 0.5 mm strip was cut from the filter and completely immersed in 0.5 mL of M2Dx prepolymer solution to obtain concentrated particle-containing M2Dx solution.
[0264] The standard spectrum was obtained by measuring an M2Dx prepolymer solution containing 1 mg / mL lyophilized particles (with PEG4000), which was confirmed to have approximately 50% light transmittance at 426 nm after being polymerized into a gel. The standard absorbance value of the secondary peak was determined to be approximately 0.5 at 560 nm. Test articles were then prepared by gradually adding a small amount of concentrated particle-containing M2Dx solution of unknown concentration to 1.5 mL of M2Dx stock until the spectrum and secondary absorbance matched the standard, as measured on an Agilent 8453 spectrophotometer.
[0265] Evaluation of M2Dx prepolymer The particle-containing M2Dx solutions were evaluated by spectroscopic measurements and visual inspection. The spectra of the test items were examined during the particle consolidation stage and the M2Dx solutions were visually inspected.
[0266] result All test articles containing free dye could be homogeneously resuspended in the M2Dx prepolymer. No significant anomalies were observed upon visual inspection of the particle-containing prepolymer. As shown in Figure 25, the spectra of all test articles had the same characteristic peaks as zinc(II) 5,10,15,20-(tetraphenyl)porphyrin.
[0267] Polymerization of M2Dx Matrix The contact lens prototypes were polymerized in a mold assembled by sandwiching an aluminum frame with a designated volume of 1 mL using two glass slides. An oil-based mold release agent was sprayed on the frame and slides as a mold release agent, after which the mold was assembled. The mold was placed in a plastic bag and pressure was applied to the slide using four clamps to prevent leakage. Once the spectral measurements were performed, 10 μl of the photoinitiator 2-hydroxy-2-methylpropiophenone (Darocure™ 1173) was immediately added to the particle-containing M2Dx solution. A 3 mL syringe was then used to inject the solution into the mold through the injection port. Once the solution was filled, the bag was vacuum sealed using a vacuum sealer and placed in a UV chamber. The M2Dx solution was UV cured in the plastic bag for 10 minutes. Once the curing process was completed, the gel was carefully transferred from the mold into a scintillation vial containing 20 mL of deionized water using blunt tweezers.
[0268] Evaluation of M2Dx polymer The particle-containing M2Dx polymers were evaluated by spectral measurements and visual inspection. To obtain good spectral data, an empty M2Dx gel made using the same procedure was used to blank the spectrophotometer, and a Kimwipe was used to wipe the gel to remove water before spectral measurement. All prototypes were visually inspected to ensure high quality test items without visual anomalies. To correct for the baseline of the samples, the average value from 700 to over 1000 nm was taken for each sample and this was subtracted from the absorbance value at each wavelength. All test items containing free dye were able to be UV cured into M2Dx polymer. Figure 26 shows a photograph of the M2Dx polymer gels representing all samples tested, no significant anomalies were observed. However, the degree of tinting of all test items was different. UV-Vis absorbance spectra of each M2Dx polymer containing different composite particles were obtained and are shown in Figure 27A. The transmission spectra are shown in Figure 27B.
[0269] Considering that the M2Dx polymer itself does not have optical and visual properties, the absorbance peaks of the test items may be due to the incorporation of different particles. The incorporation of the particles of the present disclosure could give an absorbance corresponding to that of the dye encapsulated in the composite particles.
[0270] (Example 17) Optical filtering in contact lenses. This study demonstrates the optical properties of various composite particles of the present disclosure incorporated into a representative silicone hydrogel lens. The purpose is to compare test article samples for their ability to limit light exposure, for example, in the blue light hazard region of the spectrum (400-450 nm). Test articles were created by adding dry particle composites to M2Dx formulation monomers, which were subsequently polymerized to create lenses. The spectra of contact lenses containing the test articles showed blue light hazard blocking, and all test articles showed the same characteristic peaks as the control article containing free zinc(II) 5,10,15,20-(tetraphenyl)porphyrin (Zn(II)TPP) dye, suggesting that encapsulation did not change the shape of the dye payload spectrum. In addition, encapsulation did not affect sample bandwidth, with the exception of CS28. Encapsulation using poly(dimethylsiloxane) 8000-b-poly(acrylic acid) 8000 (diblock copolymer) broadened the dye payload spectrum by 8 nm in this polymer system.
[0271] Comparison items BC01, PH01, and PN01 were used. Composite particles of the present disclosure, CS28-CS42, were made and tested as described above. M2Dx prepolymer was prepared as described above. Two control items, CS00 (free dye) and empty M2Dx polymer, were also prepared as described above and used in this study. The particles were dried with cryoprotectant PEG4000. The particle solution was passed through a 30 nm membrane filter and vacuum dried, except for PN01, which was filtered using a 10 nm membrane filter. Test items CS42 and PN01 could not be filtered using 30 nm or 10 nm membrane filters, indicating that the particles were smaller than 10 nm or had low encapsulation efficiency. As a result, CS42 and PN01 were air-dried at room temperature. M2Dx prepolymer was mixed with each particle and polymerized as described above.
[0272] The gels were measured using UV / Vis spectroscopy to assess their optical properties. A non-particle-containing M2Dx gel was used to blank the spectrophotometer. To correct the sample baseline, the average value from 700 to over 1000 nm was taken for each sample and this was subtracted from the absorbance value at each wavelength.
[0273] The optical properties of M2Dx polymer gel are summarized in Table 10.
[0274] [Table 10]
[0275] All test and control articles had consistent shape, bandwidth, and peak wavelength as the free dye in THF. A slight broadening of the bandwidth (19 nm) was observed for CS28. A characteristic peak was detected in the blue light hazard region (410-450 nm) with a peak position at 425 nm in all test and control articles. A peak shift of 3 nm compared to the free dye in THF was observed in all test and control articles due to the change in solvent system. By comparing the control and test articles, the conclusion could be confidently drawn that the absorbance spectrum of the zinc(II) 5,10,15,20-(tetraphenyl)porphyrin dye was not significantly altered by encapsulation.
[0276] (Example 18) Ethanol extraction of contact lenses containing composite particles In the manufacture of contact lenses, the manufactured contact lenses undergo a series of ethanol washing steps to remove unreacted monomers so that the lenses are safe to enter the eye. The pigments incorporated into the contact lenses via the composite particles should ideally not be extracted from the contact lenses by the ethanol washings.
[0277] Comparative items BC01, PH01, and PN01 were used. Composite particles of the present disclosure, CS28-CS42, were made and tested as described above. M2Dx prepolymer was prepared as described above. Two control items, CS00 (free dye) and blank M2Dx polymer, were also prepared as described above and used in this study.
[0278] Once the gels were made and cut to the size required for this experiment, all gels were kept in deionized (DI) water vials for 24 hours to allow them to hydrate.
[0279] The samples were removed from their water vials and placed into empty, labeled scintillation vials. At time=0, 10 mL of 25% ethanol extraction solution was poured simultaneously onto all samples and the gels were left immersed in this solution for 1 hour. At the 1 hour mark, the gels were removed from the solution and placed into water vials to quickly stop the extraction. At this point, the gels and ethanol were measured using a UV / Vis spectrometer with the appropriate blanks.
[0280] This process was repeated for the 50%, 75%, and 95% ethanol extraction steps, using a volume of 10 mL for each extraction solution. The solutions were not stirred to avoid damaging the gel, which may be susceptible to breakage when exposed to ethanol. Note that the gel was not measured after the 75% ethanol extraction because it appeared weaker and there was concern about gel breakage.
[0281] UV-Vis absorbance measurements were performed on all gels. Correction factors were applied to account for differences in the amount of particles in each gel sample. The correction factors are shown in Table 11.
[0282] [Table 11]
[0283] The ethanol absorbance readings are summarized in Table 12 below. No absorbance readings were obtained for the 25% and 50% ethanol extractions, so these results were not included. The absorbance values shown have been corrected using a correction factor, where the actual absorbance is divided by the correction factor to account for differences in the initial absorbance of the gel. The absorbance measured in the 75% and 95% washes are summed to obtain the absorbance lost in the ethanol wash. The lower total absorbance in EtOH indicates less extraction of pigment with the ethanol wash.
[0284] [Table 12]
[0285] Representative UV-Vis absorbance spectra of CS42, CS34, CS37, and CS41 gels and their corresponding 95% ethanol washes are shown in Figure 28 (A-D).
[0286] Based on the UV-Vis absorbance spectra, the composite particles of the present disclosure were able to resist ethanol leaching, especially CS28, CS34, and CS42, which outperformed the control free dye CS00.
[0287] (Example 19) Thermal stability of particles in contact lenses. Autoclaving procedures are used in contact lens manufacturing to sterilize contact lenses after packaging. Contact lens manufacturers use autoclaves to sterilize saline-soaked contact lenses. Autoclave conditions include holding samples at 121°C and 108 kPa for 30 minutes. Composite particles were incorporated into representative contact lens gels and then exposed to autoclave conditions for 30 minutes. After the autoclave process, the saline storage solutions and gels were measured with a spectrophotometer. All samples tested in this study were found to show no leaching into the saline solution. The absorbance spectra, and therefore the optical filtering capabilities of the additives, were not altered by the autoclave process.
[0288] M2Dx gels containing different composite particles were prepared as described above. Comparative items BC01 and PH01 were used. Composite particles of the present disclosure, S28-CS31 and CS33-CS41, were made and tested as described above. M2Dx prepolymer was prepared as described above. Two control items, CS00 (free dye) and empty M2Dx polymer, were also prepared as described above and used in this study.
[0289] All test items were cut into 2 cm x 2 cm gels and then added to scintillation vials containing 5 mL of saline. The samples were then subjected to a pre-set "L30 cycle" autoclave process, meaning that the samples were under sterile conditions for 30 minutes. The autoclave was an AMSCO Steris make and model.
[0290] A representative UV-Vis absorbance spectrum is shown in Figure 29. The UV-Vis absorbance of the saline solution after autoclaving was also measured. The spectrum is shown in Figure 30, but no absorbance peak corresponding to the encapsulated dye was observed.
[0291] This study showed that the autoclave process did not leach the composite particles of the present disclosure into saline. The results also showed that autoclaving did not affect the optical filter ability of the additive. The absorbance of the gel did not change significantly before or after the autoclave process.
[0292] (Example 20) Solvent Stability of Contact Lenses The manufacture of contact lenses usually involves the use of organic solvents. The main solvents include ethanol, hexanol, butoxyethanol, nonanol, and t-amyl alcohol. The particles tested and their corresponding codes are listed below. 1. CS09- Dye-encapsulated nanoparticles {Zinc(II) 5,10,15,20-(tetraphenyl)porphyrin (dye) poly(1,2-butadiene) 31,000-b-poly(methyl methacrylate) 21,500 (diblock copolymer)} 2. CS01 - Dye-encapsulated nanoparticles crosslinked via tetraethyl orthosilicate (5 times the mass of the hydrophilic block) {zinc(II) 5,10,15,20-(tetraphenyl)porphyrin (dye) poly(1,2-butadiene) 31,000-b-poly(methyl methacrylate) 21,500 (diblock copolymer)} 3. CS13 - Dye-encapsulated nanoparticles crosslinked via tetraethyl orthosilicate (5 times the mass of the hydrophilic block) and hydrochloric acid {zinc(II) 5,10,15,20-(tetraphenyl)porphyrin (dye) poly(1,2-butadiene) 31,000-b-poly(methyl methacrylate) 21,500 (diblock copolymer)} 4. PN01- Dye-encapsulated nanoparticles {Zinc(II) 5,10,15,20-(tetraphenyl)porphyrin (dye) poly(ethylene oxide) 4000-b-poly(methylethylene oxide) 3000-b-poly(ethylene oxide) 4000 (triblock copolymer)} 5. CS14 - Dye-encapsulated nanoparticles crosslinked via tetraethyl orthosilicate (5 times the mass of the hydrophilic block) and by free radical polymerization (1%) {zinc(II) 5,10,15,20-(tetraphenyl)porphyrin (dye) poly(ethylene oxide) 4000-b-poly(methylethylene oxide) 3000-b-poly(ethylene oxide) (triblock copolymer) 4000} 6. CS15 - Dye-encapsulated nanoparticles crosslinked via tetraethyl orthosilicate (5 times the mass of the hydrophilic block) and hydrochloric acid {zinc(II) 5,10,15,20-(tetraphenyl)porphyrin (dye) poly(ethylene oxide) 4000-b-poly(methylethylene oxide) 3000-b-poly(ethylene oxide) 4000 (triblock copolymer)} 7. CS16- Dye-encapsulated nanoparticles {Zinc(II) 5,10,15,20-(tetraphenyl)porphyrin (dye) poly(dimethylsiloxane) 8000-b-poly(acrylic acid) 8000 (diblock copolymer)} 8. CS17 - Dye-encapsulated nanoparticles crosslinked using tetraethyl orthosilicate (5 times the mass of the hydrophilic block) {zinc(II) 5,10,15,20-(tetraphenyl)porphyrin (dye) poly(dimethylsiloxane) 8000-b-poly(acrylic acid) 8000 (diblock copolymer)} 9. CS18- Dye-encapsulated nanoparticles {Zinc(II) 5,10,15,20-(tetraphenyl)porphyrin (dye) poly(1,2-butadiene) 15000-b-poly(acrylic acid) 6500 (diblock copolymer)} 10. CS19 - Tetraethyl orthosilicate and acid crosslinked dye encapsulated nanoparticles {Zinc(II) 5,10,15,20-(tetraphenyl)porphyrin (dye) poly(1,2-butadiene) 15000-b-poly(acrylic acid) 6500 (diblock copolymer)} 11. CS20 - Dye-encapsulated nanoparticles crosslinked by tetraethyl orthosilicate, free radicals, acid, and heat {zinc(II) 5,10,15,20-(tetraphenyl)porphyrin (dye) poly(1,2-butadiene) 15000-b-poly(acrylic acid) 6500 (diblock copolymer)} 12. CS21 - Tetraethyl orthosilicate and dye-encapsulated nanoparticles crosslinked by free radical reaction {zinc(II) 5,10,15,20-(tetraphenyl)porphyrin (dye) poly(1,2-butadiene) 15000-b-poly(acrylic acid) 6500 (diblock copolymer)} 13. CS22- Tetraethyl orthosilicate, free radical, and thermally crosslinked dye-encapsulated nanoparticles {zinc(II) 5,10,15,20-(tetraphenyl)porphyrin (dye) poly(1,2-butadiene) 15000-b-poly(acrylic acid) 6500 (diblock copolymer)} 14. CS04 - Dye-encapsulated nanoparticles crosslinked with tetraethyl orthosilicate (5 times the mass of the hydrophilic block) {zinc(II) 5,10,15,20-(tetraphenyl)porphyrin (dye) poly(1,2-butadiene) 15000-b-poly(acrylic acid) 6500 (diblock copolymer)} 15. CS23 - Dye-encapsulated nanoparticles crosslinked with tetraethyl orthosilicate (20 times the mass of the hydrophilic block) {zinc(II) 5,10,15,20-(tetraphenyl)porphyrin (dye) poly(1,2-butadiene) 15000-b-poly(acrylic acid) 6500 (diblock copolymer)} 16. CS27- Dye-encapsulated nanoparticles {zinc(II) 5,10,15,20-(tetraphenyl)porphyrin (dye) poly(vinyl alcohol) 2300-b-poly(methyl methacrylate) 25000 (diblock copolymer)} shell crosslinked with tetraethyl orthosilicate (5 times the mass of the poly(acrylic acid) block) in the presence of 0.001M hydrochloric acid by heating at 80°C for 24 hours. 17. CS28- Dye-encapsulated nanoparticles {zinc(II) 5,10,15,20-(tetraphenyl)porphyrin (dye) poly(dimethylsiloxane) 8000-b-poly(acrylic acid) 8000 (diblock copolymer)} shell crosslinked with tetraethyl orthosilicate (5 times the mass of poly(acrylic acid) block) in the presence of 0.001M hydrochloric acid by heating at 80°C for 24 hours. 18. CS29- Dye-encapsulated nanoparticles {zinc(II) 5,10,15,20-(tetraphenyl)porphyrin (dye) poly(methyl methacrylate) 7400-b-poly(acrylic acid) 24300 (diblock copolymer)} shell crosslinked with tetraethyl orthosilicate (5 times the mass of the poly(acrylic acid) block) in the presence of 0.001M hydrochloric acid by heating at 80°C for 24 hours. 19. CS30- Dye-encapsulated nanoparticles {zinc(II) 5,10,15,20-(tetraphenyl)porphyrin (dye) poly(1,2-butadiene) = -b-poly(acrylic acid) 6500 (diblock copolymer)} shell crosslinked with tetraethyl orthosilicate (5 times the mass of poly(acrylic acid) block) in the presence of 0.001M hydrochloric acid by heating at 80°C for 24 hours. 20. CS31- Dye-encapsulated nanoparticles {zinc(II) 5,10,15,20-(tetraphenyl)porphyrin (dye) poly(dimethylsiloxane) 5000-b-poly(ethylene oxide) 2100 (diblock copolymer)} shell crosslinked with tetraethyl orthosilicate (5 times the mass of poly(ethylene oxide) block) in the presence of 0.001M hydrochloric acid by heating at 80°C for 24 hours. 21. CS33- Dye-encapsulated nanoparticles {zinc(II) 5,10,15,20-(tetraphenyl)porphyrin (dye) poly(styrene) 1300-b-poly(ethylene oxide) 5600 (diblock copolymer)} shell crosslinked with tetraethyl orthosilicate (5 times the mass of poly(ethylene oxide) block) in the presence of 0.001M hydrochloric acid by heating at 80°C for 24 hours. 22. CS34- Dye-encapsulated nanoparticles {zinc(II) 5,10,15,20-(tetraphenyl)porphyrin (dye) poly(n-butyl acrylate) 7500-b-poly(acrylic acid) 5500 (diblock copolymer)} shell crosslinked with tetraethyl orthosilicate (5 times the mass of poly(acrylic acid) block) in the presence of 0.001M hydrochloric acid by heating at 80°C for 24 hours. 23. CS35- Dye-encapsulated nanoparticles {zinc(II) 5,10,15,20-(tetraphenyl)porphyrin (dye) poly(methyl methacrylate)3000-b-poly(ethylene oxide)3000 (diblock copolymer)} shell crosslinked with tetraethyl orthosilicate (5 times the mass of poly(ethylene oxide) block) in the presence of 0.001M hydrochloric acid by heating at 80°C for 24 hours. 24. CS36- Dye-encapsulated nanoparticles {zinc(II) 5,10,15,20-(tetraphenyl)porphyrin (dye) poly(1,4-butadiene) 9000-b-poly(acrylic acid) 3500 (diblock copolymer)} shell crosslinked with tetraethyl orthosilicate (5 times the mass of the poly(acrylic acid) block) in the presence of 0.001M hydrochloric acid by heating at 80°C for 24 hours.
[0293] The composite particles are prepared and dried by a suitable method as described above.
[0294] This study was conducted over the course of three experiments to determine the effect of solvent washing on synthetic polymeric micelle formulations. Samples were made in tetrahydrofuran (THF) containing both block copolymer and dye at a concentration of 2,500 mg / mL. 2 ml of stock was mixed with 18 ml of deionized water using FNP to obtain a final concentration of 250 mg / mL. In FNP, 16 ml of water was stirred, then 2 ml of water and 2 ml of stock solution were added via syringe using a metal confined impinging jet (CIJ) mixer device to form the synthetic polymeric micelles. After formation, all samples were centrifuged at 4000 RPM for 1 hour using an 80-2 electronic centrifuge. These samples were then exposed to a solution of 50% ethanol to obtain an understanding of the ethanol exposure (0.5 mL of sample to 0.5 mL of ethanol). The resulting samples were then vortexed for 15 seconds and left overnight. The solutions were then compared using a spectrophotometer and visual inspection. All dynamic light scattering (DLS) samples were prepared by diluting the composite particle samples (100x) and filtering through a 450 nm filter and analyzed for particle size measurement using a Brookhaven™ BI-200SM instrument. In preparation for visual characterization, the samples had to be photographed individually in a photo box, including the stock and ethanol-treated samples. The first experiment was performed to determine which composite particles could withstand exposure to 50% ethanol overnight. The samples that best withstood ethanol exposure were tested with more solvent. Additionally, stock solutions were measured (100x dilution) to compare the loss of absorbance of the samples.
[0295] The second experiment used the test items from the first experiment that best withstood the ethanol wash, as judged by absorbance and visual inspection. These test items were then further tested in this experiment to determine the effect of multiple solvents used in the manufacture of contact lenses on the various composite particle formulations. The following test items were used in this experiment: CS17, CS20, CS22, and CS04. To test the effect of the solvent on the composite particle solutions, first, 0.5 mL of each sample was placed in a centrifuge tube for each solvent being tested. Each sample was added with 0.5 mL of either hexanol, butoxyethanol, methanol, t-amyl alcohol, or nonanol to make a 50% alcohol solution. All the resulting samples were then vortexed for 15 seconds and left overnight before centrifuging the samples. The samples were then analyzed for survivability by visual characteristics, absorbance data, and DLS data. DLS samples were prepared by diluting (100x) the synthetic polymeric micelle samples and filtering through a 450 nm filter, and representative size measurements were obtained using DLS. Samples for spectrophotometer UV-Vis measurements (Agilent) were diluted to obtain representative absorbance measurements. In preparation for visual characterization, samples had to be photographed individually in a photobox and compared to stock samples.
[0296] The UV-Vis spectra of representative composite particles in ethanol are shown in panels A-F of Figure 31. The UV-Vis spectra of representative composite particles in various solvents are shown in panels G-I of Figure 31.
[0297] DLS data for representative composite particles CS17, CS20, CS22, and CS04 are shown in Tables 13, 14, 15, and 16, respectively.
[0298] [Table 13]
[0299] [Table 14]
[0300] [Table 15]
[0301] [Table 16]
[0302] The stability results in various solvents are summarized in Table 17. The criteria for Satisfactory (S) / Improved (I) were based on a combination of visual inspection, UV-Vis absorbance, and DLS results of the samples, with Satisfactory samples being comparable to CS00 and Improvements providing improved performance compared to CS00. For visual inspection, the solution color of CS00 was compared to the composite particles to determine the relative concentration of the dye. For V-Vis absorbance, the solution absorbance of CS00 was compared to the composite particles to determine the relative concentration of the dye. The DLS results of the composite particles indicated whether the particles were stable in the solvents tested. Based on the visual inspection, UV-Vis absorbance, and DLS results, the composite particles of the present disclosure were able to withstand solvent exposure better than CS00 and showed improvement over systems containing only free dye, including CS04, CS17, CS19, CS20, CS22, CS28, CS29, CS31, CS33, CS34, and CS35.
[0303] [Table 17]
[0304] Example 21 Photobleaching of composite particles in contact lenses. Photobleaching is a photochemical change of a dye or fluorophore molecule such that the absorbance spectrum of the compound is permanently changed or destroyed.Normal wear of contact lenses may expose the lenses to various UV conditions, so it may be desirable for composite particles incorporated into contact lenses to have some resistance to photobleaching.However, this is not an absolute criterion for composite particles used in contact lenses, because normal daily wear of contact lenses is likely to expose the lenses and composite particles only to UV conditions that are much milder and significantly weaker than the photobleaching conditions used in this experiment.
[0305] Comparative items BC01, PH01, and PN01 were used. Composite particles of the present disclosure, CS28-CS42, were made and tested as described above. M2Dx prepolymer was prepared as described above. Two control items, CS00 (free dye) and blank M2Dx polymer, were also prepared as described above and used in this study.
[0306] The dried particles were resuspended in a stock of M2Dx, and then the particles were diluted in another M2Dx solution until an absorbance of approximately 0.5 was measured in the second peak of the spectrophotometer. Next, 12.5 μL of 2-hydroxy-2-methylpropiophenone (DAROCUR 1173) was added to 3 mL of M2Dx solution as a photoinitiator. The M2Dx was then polymerized in a UV reactor for 10 minutes and stored in DI water. The spectrophotometer was blanked using M2Dx without dye or nanoparticles.
[0307] photobleaching In this experiment, all samples were exposed to UV light (approximately 250 nm) using a UV reaction chamber. After exposure, each sample was measured using an Agilent spectrophotometer to determine changes in optical filter capacity. This was done over a series of time points, one minute at a time. Samples were photobleached for a total of five minutes. Photobleaching was measured in the gel every minute up to five minutes.
[0308] The UV-Vis absorbance spectrum of a representative gel (containing CS35) is shown in Figure 32. The rate of photobleaching of each composite particle in contact lens gel was found to follow second order kinetics using the peak absorbance at 425 nm. The rate of photobleaching (k) of second order kinetics is shown in Table 18, where a smaller k indicates a slower rate of photobleaching. Most of the composite particles of the present disclosure showed slower photobleaching rates compared to the free dye (CS00) and comparative examples BC01 and PN01.
[0309] [Table 18]
[0310] Based on the secondary photobleaching rate, the composite particles of the present disclosure were able to resist photobleaching. These embodiments are CS28, CS29, CS30, CS31, CS32, CS33, CS34, CS35, CS36, CS37, CS38, CS39, CS40, CS41, and CS42. In particular, some composite particles of the present disclosure were better at resisting photobleaching than the control item free dye CS00, showing an improvement over systems containing only free dye. These embodiments are CS28, CS29, CS30, CS31, CS32, CS33, CS34, CS35, CS36, CS37, CS38, CS39, CS41, and CS42.
[0311] Furthermore, comparative example PN01 was unable to resist photobleaching.
[0312] Example 22 Shelf life Storage stability Contact lenses for commercial use are typically soaked in phosphate buffered saline (PBS) and packaged in blister packs, which allows them to be sterilized and stored for a period of time. In this study, various composite particles incorporated into M2Dx gel were exposed to saline after autoclaving to simulate storage conditions for sterilized contact lenses. This study followed the guidelines of the Contact Lens Color Additive Petition created by the US Food and Drug Administration to evaluate particle migration. Particle leaching was determined by visual inspection and UV-Vis spectroscopy. The saline used to contain the prototypes was measured to determine the presence of particles. An accelerated aging technique was applied to reduce the saline exposure time. All test and control articles were free of leaching after 136.5 hours of saline exposure at 50°C, as no absorbance was measured at the dye peak wavelength of 425 nm. In addition, no visual abnormalities were observed in either the gel or the saline. Therefore, it could be concluded that exposure to saline did not result in particle migration and all test and control articles passed this shelf life study.
[0313] According to the FDA, to simulate daily wear contact lenses containing color additives, prototypes must be immersed in saline or PBS at 37 degrees Celsius for 14 days. In addition, migration studies were performed using 0.9% (by weight) saline or PBS with a surface area to volume ratio of 120 cm. 2 Lens vs. 20 mL extract (i.e. 6 cm 2 The test should be performed at 100 µg / mL.
[0314] To accelerate saline exposure, we implemented an FDA-approved accelerated aging technique. In this study, we evaluated the prototypes at a gel surface area to saline ratio of 6 cm. 2The experiment was carried out in 0.9% saline at 100 / mL. The test articles were heat treated at 50 degrees Celsius for 136.5 hours. The saline was measured using a spectrophotometer after heat treatment to detect particle migration.
[0315] The stability of the nanoparticles is evaluated using the following criteria: 1. The aged particle filled contact lens prototypes should have the same / similar spectral and optical properties as the reference. 2. The aged particle-filled contact lens prototypes should have no noticeable abnormalities (yellowing, cloudiness, darkening, etc.). 3. The spectrum of the saline solution used for the extraction of the prototype should not contain any signals of free dye or particles. 4. Free dye should not precipitate in saline solution.
[0316] Comparative items BC01, PH01, and PN01 were used. Composite particles of the present disclosure, CS28-CS42, were made and tested as described above. M2Dx prepolymer was prepared as described above. Two control items, CS00 (free dye) and blank M2Dx polymer, were also prepared as described above and used in this study.
[0317] The contact lens prototypes were polymerized in a mold assembled by sandwiching an aluminum frame with a designated volume of 1 mL using two glass slides. An oil-based mold release agent was sprayed on the frame and slides as a mold release agent, after which the mold was assembled. The mold was placed in a plastic bag and pressure was applied to the slide using four clamps to prevent leakage. Once the spectral measurements were performed, 10 μl of the photoinitiator 2-hydroxy-2-methylpropiophenone (Darocure 1173) was immediately added to the particle-containing M2Dx solution. A 3 mL syringe was then used to inject the solution into the mold through the injection port. Once the solution was filled, the bag was vacuum sealed using a vacuum sealer and placed in a UV chamber. The M2Dx solution was UV cured in the plastic bag for 10 minutes. Once the curing process was complete, the gel was carefully transferred from the mold into a scintillation vial containing 20 mL of deionized water using blunt tweezers.
[0318] Autoclaving The prototypes were autoclaved for 30 minutes in 5 mL of saline at 121 degrees Celsius and 108 kPa using an AMSCO Steris. Composite particles CS28, 29, 30, 31, and 33-41, and comparative examples BC01 and PH01 were autoclaved.
[0319] Accelerated Aging Every 2 cm x 2 cm prototype was cut into 9 small pieces, each with a length, width, and height of 0.67 cm, 0.67 cm, and 0.1 cm, respectively. The total surface area of each test item was 6.30 cm 2 The surface area to volume ratio is 6 cm 2 The gel was completely immersed in 1.05 mL of saline to obtain a 1.0% solubility in 100% water / mL. The prototype was then heated in a Thermo Scientific oven at 50 degrees Celsius for 136.5 hours. The required heating temperature and time were calculated using an accelerated aging technique based on the Arrhenius theory. After the specified time, the sample was removed from the oven and cooled to room temperature before spectral measurements were taken.
[0320] Spectral measurements The saline content of the samples after heating was measured using a spectrophotometer to identify the presence of particles or dyes that had leached from the gel. The saline used to contain the empty M2Dx was used to blank the spectrophotometer and heat treated in the same way as the other samples.
[0321] result No signal was observed in the visible light region of the saline solution used to contain the prototypes after aging for all test and control items, all as shown in Figure 33. Some small peaks can be seen at 368, 486, 637, and 656 nm due to surface imperfections (scratches) on the plastic disposable cuvette. The gels and saline solutions were visually inspected after aging and no visual anomalies (precipitation, yellowing, cloudiness, etc.) were observed.
[0322] Spectral data suggested that saline exposure did not move particles out of the gel into solution, as no absorbance was measured at the Zn(II)TPP peak wavelength of 425 nm. If free dye leached out of the gel, its hydrophobicity would render it insoluble in saline and undetectable. The saline was visually inspected for solids, but it does not appear that any unencapsulated dye was released into the saline. No water-soluble species were leached out of the gel, as no dye absorbance peak was detected at 425 nm by spectrophotometer.
[0323] According to FAD regulatory standards, all particles were shown to be storable at room temperature.
[0324] Example 23 Code names for examples of composite particles of the present disclosure Table 19 shows a list of examples of composite particles of the present disclosure.
[0325] [Table 19A]
[0326] [Table 19B]
[0327] [Table 19C]
[0328] [Table 19D]
[0329] [Table 19E]
[0330] [Table 19F]
[0331] [Table 19G]
[0332] While the present disclosure has been described with reference to what are presently considered to be the preferred examples, it is to be understood that the invention is not limited to the disclosed examples, but rather, the invention is intended to cover various modifications and equivalent arrangements included within the spirit and scope of the appended claims.
[0333] All publications, patents, and patent applications mentioned are herein incorporated by reference in their entirety to the same extent as if each individual publication, patent, or patent application was specifically and individually indicated to be incorporated by reference in its entirety. [Explanation of symbols]
[0334] 10. Dye Encapsulation Process 12 Dye 14 Amphiphilic block copolymer 1 16 Organic Solvents 18 mixture 20 water 22 Composite particles 24 Hydrophobic Core 26 Hydrophilic Shell
Claims
1. 1. A contact lens comprising one or more composite particles, the one or more composite particles being A hydrophobic dye; Hydrophobic dye-encapsulated amphiphilic block copolymers and wherein the hydrophobic dye has an absorbance ranging from the ultraviolet to the infrared region of the electromagnetic spectrum.
2. The contact lens of claim 1 , wherein the amphiphilic block copolymer is crosslinked.
3. 3. The contact lens of claim 1 or 2, wherein the hydrophobic dye is a laser dye or an absorber dye.
4. Hydrophobic dyes include coumarin, fluorescein, rhodamine, pyrromethene, cyanine, carbocyanine, flavin, oxazine, carbazine, stilbene, diphenylstilbene, oxazole, diphenyl, terphenyl, quaterphenyl, polyphenyl, phenyloxazone, phenoxazonium, pyridine, pyridinium, carotenoid, retinoid, porphyrin, phthalocyanine, benzophenone, metal oxide, benzotriazole, tocopherol, tocotrienol, anthracene, perylene, polycyclic aromatic carbon.
4. The contact lens of claim 1, wherein the pigment is selected from the group consisting of aryl hydrides (PAHs), polyenes, cholines, chlorines, corphines, indolenines, chlorophylls, azo dyes, polymethines, diarylmethanes, triarylmethanes, polyenes, anthracinediones, pyrazolones, anthraquinones, pyrans, phenothiazines, triazines, oxalanilides, acridines, benzanthrones, BODIPY, AzaBODIPY, and combinations thereof.
5. 5. The contact lens of claim 4, wherein the hydrophobic dye is selected from BODIPY, AzaBODIPY, tetraphenylporphyrin, phthalocyanine, naphthalocyanine, coumarin, benzotriazole, tocopherol, tocotrienol, carotenoid, anthracene, perylene, metal oxide, and combinations thereof.
6. The contact lens of any one of claims 1 to 5, wherein the amphiphilic block copolymer is biocompatible.
7. The contact lens of claim 1 , wherein the amphiphilic block copolymer is a diblock copolymer.
8. 8. The contact lens of claim 1, wherein the amphiphilic block copolymer is a poly(alkyl acrylate)-based copolymer, a poly(alkyl methacrylate)-based copolymer, a poly(acrylic acid)-based copolymer, a poly(methacrylic acid)-based copolymer, a polydiene-based copolymer, a poly(N-isopropylacrylamide)-based copolymer, a polyethylene glycol-based copolymer, a poly(methylene indane)-based copolymer, a polysiloxane-based copolymer, a polystyrene-based copolymer, a substituted polystyrene-based copolymer, a poly(vinylpyridine)-based copolymer, a poly(vinyl alcohol)-based copolymer, a poly(alkyl acrylic acid)-based copolymer, a poly(alkylene oxide)-based copolymer, a poly(dialkylsiloxane)-based copolymer, a poly(olefin)-based copolymer, a poly(alkylene oxide diacrylate)-based copolymer, a poly(butanediol diacrylate)-based copolymer, or a combination thereof.
9. Amphiphilic block copolymers have been developed, such as poly(1,2-butadiene)-b-poly(acrylic acid), poly(1,2-butadiene)-b-poly(ethylene oxide), poly(1,2)-butadiene)-b-poly(methacrylic acid), poly(1,2-butadiene)-b-poly(methyl methacrylate), poly(1,2-butadiene)-b-poly(vinyl alcohol), poly(1,2-butadiene-co-1,4-butadiene)-b-poly(acrylic acid), poly(1,2- Butadiene-co-1,4-butadiene)-b-poly(ethylene oxide), poly(1,2-butadiene-co-1,4-butadiene)-b-poly(methacrylic acid), poly(1,2-butadiene-co-1,4-butadiene)-b-poly(vinyl alcohol), poly(1,4-butadiene)-b-poly(acrylic acid), poly(1,4-butadiene)-b-poly(ethylene oxide), poly(1,4-butadiene)-b-poly(methacrylic acid), poly(1,4-butadiene)-b-poly(vinyl alcohol), poly(dimethylsiloxane)-b-poly(acrylic acid), poly(dimethylsiloxane)-b-poly(ethylene oxide), poly(dimethylsiloxane)-b-poly(methacrylic acid), poly(dimethylsiloxane)-b-poly(n-butyl acrylate), poly(ethylene oxide)-b-poly(butadiene), poly(ethylene oxide)-b-poly(dimethylsiloxane), poly(ethylene oxide)-b-poly(meth poly(ethylene oxide)-b-poly(n-butyl acrylate), poly(ethylene oxide)-b-poly(styrene), poly(ethylene oxide)-b-poly(tert-butyl methacrylate), poly(methyl methacrylate)-b-poly(acrylic acid), poly(methyl methacrylate)-b-poly(dimethylsiloxane), poly(methyl methacrylate)-b-poly(ethylene oxide), poly(methyl methacrylate)-b-poly(methacrylic acid), poly(methyl methacrylate)-b-poly(styrene), poly(n-butyl acrylate)-b-poly(acrylic acid), poly(propylene oxide)-b-poly(butadiene), poly(propylene oxide)-b-poly(dimethylsiloxane), poly(propylene oxide)-b-poly(methyl methacrylate), poly(propylene oxide)-b-poly(n-butyl acrylate), poly(propylene oxide)-b-poly(styrene), poly(propylene oxide poly(vinyl alcohol)-b-poly(tert-butyl methacrylate), poly(vinyl alcohol)-b-poly(butadiene), poly(vinyl alcohol)-b-poly(dimethylsiloxane), poly(vinyl alcohol)-b-poly(methyl methacrylate), poly(vinyl alcohol)-b-poly(n-butyl acrylate), poly(vinyl alcohol)-b-poly(styrene), poly(vinyl alcohol)-b-poly(tert-butyl methacrylate), poly(1,2-butadiene), 15000 -b-Poly(acrylic acid) 6500 , poly(1,4-butadiene) 9000 -b-Poly(acrylic acid) 3500 , poly(dimethylsiloxane) 5000 -b-Poly(ethylene oxide) 2100 , poly(dimethylsiloxane) 8000 -b-Poly(acrylic acid) 8000 , poly(methyl methacrylate) 3000 -b-Poly(ethylene oxide) 3000 , poly(methyl methacrylate) 7400 -b-Poly(acrylic acid) 24300 , poly(n-butyl acrylate) 7500 -b-Poly(acrylic acid) 5500 ,polystyrene) 1300 -b-Poly(ethylene oxide) 5600 , poly(vinyl alcohol) 2300 -b-Poly(methyl methacrylate) 25000 , poly(vinyl alcohol) 2500 -b-Poly(styrene) 12500 9. The contact lens of claim 1, wherein the fluororesin is selected from the group consisting of fluororesin, fluorosalicylic acid ...
10. 10. The contact lens of any one of claims 1 to 9, wherein the amphiphilic block copolymer is end-functionalized, optionally the amphiphilic block copolymer is acrylate-terminated, alkyl acrylate-terminated, methacrylate-terminated, alkyl methacrylate-terminated, or a combination thereof.
11. 11. The contact lens of any one of claims 1 to 10, wherein the amphiphilic block copolymer is crosslinked using a crosslinking method selected from dialdehyde crosslinking, diamine crosslinking, diol crosslinking, ester crosslinking, free radical initiated alkene polymerization, Q-ammonium crosslinking, silane crosslinking, trialdehyde crosslinking, triamine crosslinking, triol crosslinking, urethane crosslinking, and combinations thereof.
12. A contact lens according to any one of claims 1 to 11, wherein the composite particles have a diameter of from 1 to 600 nanometers.
13. The change in the UV-Vis transmittance spectrum of the composite particles was 12.8mW / cm 2 13. The contact lens of claim 1, wherein the optical transparency of the contact lens is less than 80%, less than 70%, less than 60%, less than 50%, or less than 40% after photobleaching by UV exposure at 250 nm for 1 minute, 3 minutes, 5 minutes, 10 minutes, or 15 minutes.
14. 2. The contact lens of claim 1, wherein the maximum UV-Vis absorbance of the composite particles after autoclaving in aqueous solution at 108 kPa and 121° C. is at least 50%, 60%, 70%, 80%, or 90% of the maximum UV-Vis absorbance before autoclaving.
15. 2. The contact lens of claim 1, wherein the UV-Vis absorbance spectrum of the composite particles after ethanol washing in 25% v / v, 50% v / v, 75% v / v or 95% v / v ethanol in water for 1 hour is substantially unchanged.
16. 16. The contact lens of claim 1, wherein the composite particles are storage stable in saline at 50° C. for at least 1 day, at least 3 days, at least 4 days, at least 5 days, at least 125 hours, at least 130 hours, or at least 136 hours.
17. 12.8mW / cm 2 17. The contact lens of claim 1, wherein the change in maximum UV-Vis transmittance of the composite particle after photobleaching after 1 minute, 3 minutes, 5 minutes, 10 minutes, or 15 minutes of UV exposure at 250 nm is less than the change in maximum UV-Vis transmittance of the hydrophobic dye alone after photobleaching after 1 minute, 3 minutes, 5 minutes, 10 minutes, or 15 minutes of UV exposure at 250 nm, respectively.
18. 18. A contact lens according to any one of claims 1 to 17, which is based on a hydrogel or silicone hydrogel.
19. 12.8mW / cm for 1, 3, 5, 10, or 15 minutes 2 The maximum UV-Vis absorbance of contact lenses after photobleaching with 250 nm UV was 12.8 mW / cm 2 19. The contact lens of claim 1, wherein the UV-Vis absorbance at 250 nm is at least 50%, 60%, 70%, 80%, or 90% of the maximum UV-Vis absorbance before UV exposure.
20. 20. The contact lens of claim 1, wherein the UV-Vis absorbance spectrum of the contact lens is substantially unchanged after autoclaving at 121° C. at 108 kPa in aqueous solution.
21. 21. The contact lens of any one of claims 1 to 20, wherein the maximum UV-Vis absorbance of the contact lens after 1 hour of ethanol washing with 25% v / v, 50% v / v, 75% v / v or 95% v / v ethanol in water is at least 50%, 60%, 70%, 80%, or 90% of the maximum UV-Vis absorbance before the ethanol wash.
22. 22. The contact lens of any one of claims 1 to 21, wherein the maximum UV-Vis absorbance of the contact lens after storage in saline at 50°C for at least 1 day, at least 3 days, at least 4 days, at least 5 days, at least 125 hours, at least 130 hours, or at least 136 hours is at least 50%, 60%, 70%, 80%, or 90% of the maximum UV-Vis absorbance before storage.
23. 23. The contact lens of claim 1, wherein substantially no leaching of the composite particles from the contact lens is observed over time, exposure to organic solvents, or temperature changes.
24. 24. A method of optical filtering comprising the step of selectively blocking optical radiation using a contact lens according to any one of claims 1 to 23.
25. 25. The method of claim 24, wherein the light radiation is selected from UV light, blue light, and combinations thereof.
Citation Information
Patent Citations
Contact lens with improved, multiple and integrated effects
CN107219639A
Colored contact lens and its production
JP1994347728A
Production of colored contact lens
JP1995033808A
Aqueous colorant dispersion
JP2005263953A
antibacterial pigment
JP2006523735A